Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 196175007 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "License is CC0 1.0", "OccurrenceStatus is Present" ] } The dataset includes 196175007 records from 10273 constituent datasets: 1211 records from CCBER Herpetology Collection. 2 records from A new four-pored Amphisbaena (Squamata: Amphisbaenidae) from northeastern Brazil. 359 records from HogWatch Scotland Project - West European hedgehog records between 2019 and 2021. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 218 records from Land and freshwater molluscs of Northern Spain. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 1 records from Review of the genus Pogonolaelaps Nemati & Gwiazdowicz (Acari: Laelapidae) with description of a new species from Iran. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 1 records from A new distinctive species of Barydesmus (Diplopoda, Polydesmida, Platyrhacidae) from Ecuador, with an annotated bibliographical checklist of the American Platyrhacidae. 9883 records from University of Nebraska State Museum Birds Collection. 30730 records from University of California Santa Barbara Invertebrate Zoology Collection. 7 records from A review of the taxonomy and osteology of the Rhombophryne serratopalpebrosa species group (Anura: Microhylidae) from Madagascar, with comments on the value of volume rendering of micro-CT data to taxonomists. 2 records from Neue Milbenarten aus Kärnten. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 4 records from Two new species and new records of the Pselaphodes - complex of genera from China (Coleoptera: Staphylinidae: Pselaphinae). 4 records from Discovery of the male of Colletes yanruae from Yunnan, China (Hymenoptera: Apoidea: Colletidae). 29 records from Review of Palpostilpnus Aubert (Hymenoptera, Ichneumonidae, Phygadeuontinae), with the description of ten new species. 2 records from Vietnamella chebalingensis, a new species of the family Vietnamellidae (Ephemeroptera) from China based on morphological and molecular data. 1 records from Taxonomic notes on Sarju Ghauri, 1977 (Hemiptera: Heteroptera: Pentatomidae) with description of a new species from India. 1 records from A new species of Cladotanytarsus (Lenziella) from Oregon supports the systematic concept of the subgenus (Diptera: Chironomidae). 3 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 2 records from A review of the genus Labeo (Teleostei: Cyprinidae) in Sri Lanka. 2 records from Papuaneon, a new genus of jumping spiders from Papua New Guinea (Araneae: Salticidae: Neonini). 3825 records from UTEP Invertebrates (Arctos). 40 records from Rivaling the World’s Smallest Reptiles: Discovery of Miniaturized and Microendemic New Species of Leaf Chameleons (Brookesia) from Northern Madagascar. 112 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 10 records from Additions to the Flora of China: seven new species of Elatostema (Urticaceae) from the karst landscapes of Guangxi and Yunnan. 3 records from Taxonomic revision of the species of Colletes Latreille, 1802 (Hymenoptera: Colletidae: Colletinae) found in Chile. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 10 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 10 records from Seven new species of Australian peacock spiders (Araneae: Salticidae: Euophryini: Maratus Karsch, 1878). 5 records from A new deep-water species of Alpheopsis Coutière, 1897 from the Indo-West Pacific (Decapoda: Alpheidae). 12 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 10 records from New species of Phaloria (Orthoptera: Phalangopsidae: Phaloriinae) from West Papua (Indonesia). 7 records from Revision of Chaetacanthus Seidler, 1922 (Annelida, Phyllodocida, Polynoidae). 2 records from Review of the New World genus Nanium Townes, 1967 (Hymenoptera: Ichneumonidae: Ctenopelmatinae), with two new species from the Neotropical region. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 3786 records from Vascular plants of Amrum 2007-2008. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 3 records from The interesting and complex tribe Oxycoleini (Coleoptera, Cerambycidae): a new genus, new species, and taxonomic notes. 21 records from Taxonomic revision of Ceropegia sect. Huernia (Asclepiadoideae, Apocynaceae) in Saudi Arabia with three new combinations. 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 77 records from Identity of parasitoid wasps (Hymenoptera, Braconidae and Eulophidae) reared from aquatic leaf-mining flies (Diptera, Ephydridae) on invasive Brazilian waterweed Egeria densa in South Africa. 1 records from Happywhale - Green Sea Turtle in North Pacific Ocean. 3 records from Mangelia (Gastropoda, Conoidea) species of the Turkish coasts with description of Mangelia vanaartseni sp. nov.. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 47 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 14 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 302 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 9 records from Contribution to the knowledge of the dentipes group of the genus Brachiacantha (Coleoptera: Coccinellidae). 48 records from Identity of bryozoan species described by Jullien & Calvet from the Bay of Biscay historically attributed to Smittia. 9 records from Hemigrammus ataktos: a new species from the rio Tocantins basin, central Brazil (Characiformes: Characidae). 1618 records from Naturalis Biodiversity Center (NL) - Crustacea. 17 records from The West Palaearctic Dineura species, focussing on Sweden (Hymenoptera, Tenthredinidae). 4 records from Cast netting new species: Integrative taxonomy of Distichodus notospilus (Characiformes: Distichodontidae) discovers new species and overlooked areas of endemism in Central Africa. 3 records from A new species, a new combination, and a new record of Crossotarsus Chapuis, 1865 (Coleoptera, Curculionidae, Platypodinae) from China. 3 records from A new species of Protonemura Kempny, 1898 (Plecoptera: Nemouridae) from the Ishizuchi range, Shikoku, Japan. 560 records from Data from ILAM surveys conducted by ARCOS in Bugesera landscape for year 2016. 12 records from An ancient radiation: Ortholasmatine harvestmen in Asia - a new genus, three new species and a revision of the known species (Arachnida, Opiliones, Nemastomatidae). 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 1 records from The flower fly genus Eosphaerophoria Frey (Diptera, Syrphidae). 2 records from A new record of the family Isonychiidae (Insecta: Ephemeroptera) from the Western Ghats, India with a description of new species. 5 records from Discovered online: Hibiscus hareyae sp. nov. of sect. Lilibiscus (Malvaceae), threatened in coastal thicket at Lindi, Tanzania. 5 records from Seven new species and additional records of Palaearctic Leptusa, primarily from Yunnan, China (Coleoptera: Staphylinidae: Aleocharinae). 8 records from Revision Of The Australian Coccinellidae (Coleoptera). Genus Novius Mulsant Of Tribe Noviini. 18 records from Documenting new and little known leaf-mining Nepticulidae from middle and southwestern areas of the Asian continent. 400 records from 2014_nsmk_smpl_in. 3 records from Revision of the genus Polymerus (Heteroptera: Miridae) in the Eastern Hemisphere. Part 1: Subgenera Polymerus, Pachycentrum subgen. nov. and new genus Dichelocentrum gen. nov.. 2 records from A new species of Hypsohapsis (Heteroptera: Schizopteridae: Hypselosomatinae) from the Brazilian Amazon. 12273 records from Invasive Plant Atlas of the MidSouth (IPAMS). 6 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 13 records from Records Of Neoperlini (Plecoptera: Perlidae) From Brunei Darussalam And Sarawak, With Descriptions Of New Phanoperla Banks And Neoperla Needham Species. 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 4 records from A Catalogue and Historical Study of the Odonata of Ecuador. 12 records from On the taxonomy of the genera Planovalvata Dubatolov & Kishida, Stigmatophora Staudinger and Pseudomiltochrista Dubatolov & Bucsek, with description of one new species (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 1 records from Ant-like stone beetles on the roof of the world. Cephenniini of Nepal and Bhutan (Coleoptera, Staphylinidae, Scydmaeninae). 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 2 records from Tertiarius minutulus sp. nov. (Stephanodiscaceae, Bacillariophyta) - a new fossil diatom species from Lake Ohrid. 39 records from Liogenys Guérin-Méneville, 1831 (Coleoptera: Scarabaeidae: Melolonthinae Diplotaxini) from the Chacoan Province and its boundaries: taxonomic overview with four new species. 4 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 10 records from Description of six new large species of Argentinomyia Lynch-Arribalzaga, 1891 and redescription of Talahua fervida (Fluke, 1945) (Diptera, Syrphidae, Syrphinae). 1 records from A new species of Casmaria H. Adams & A. Adams, 1853 (Gastropoda, Cassidae) from the Philippines identified by molecular data. 2 records from A new species of Potentilla (Potentilleae, Rosaceae) from central China, with reference to molecular and morphological evidence. 5 records from New taxa and notes of katydids from the tribe Meconematini (Orthoptera: Meconematinae) from Brunei Darussalam (Part 2). 20 records from Morphological phylogenetic analyses and taxonomic revision of the Panorpa davidi group (Mecoptera: Panorpidae). 2 records from A new species of Girdled Lizard (Squamata: Cordylidae) from the Serra da Neve Inselberg, Namibe Province, southwestern Angola. 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 4 records from Pseudomystus Funebris, A New Species Of Catfish From Borneo (Teleostei: Bagridae). 1 records from A new arrowtooth eel of genus Meadia (Synaphobranchidae: Ilyophinae) from Vietnam, South China Sea. 1 records from Orthochaetes estrelanus sp. n., a new species from northern Portugal and new records of other Styphlini (Coleoptera, Curculionidae).. 1 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 123 records from Revision of the spider genus Mystaria Simon, 1895 (Araneae: Thomisidae) and the description of a new genus from the Afrotropical region. 4 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 20 records from Subspecies of Pleurota bicostella (Clerck, 1759) revisited and descriptions of nine new species in the P. bicostella species group (Lepidoptera: Gelechioidea Oecophoridae: Pleurotinae). 1 records from The identity of Parandra laevis Latreille, 1804 and nomenclatural changes in the Parandrinae (Coleoptera, Cerambycidae). 1 records from Two new genera and species of Fidicinini Distant, 1905 with a re-description of Nosola Stål, 1866 (Hemiptera, Auchenorrhyncha, Cicadidae). 1 records from World catalogue of the Hydrophiloidea (Coleoptera): additions and corrections II (2006 - 2010). 7 records from Unraveling Ocyptamus and the Baccha legacy (Diptera: Syrphidae): redefinition of groups and new species descriptions. 3 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 2 records from New state and island records of Coccinellidae (Coleoptera) in Hawai‘i, USA. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 46 records from Revision of the Garra species of the Hajar Mountains in Oman and the United Arab Emirates with the description of two new species (Teleostei: Cyprinidae). 4 records from Two new species of Actinocephalus (Eriocaulaceae) from Minas Gerais, Brazil. 228932 records from Mississippi Entomological Museum. 6 records from The spiny theridiid genus Meotipa Simon, 1895 in India, with description of a strange new species with translucent abdomen and a phylogenetic analysis about the genus placement (Araneae, Theridiidae). 1 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 23 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 17 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 40 records from On the taxonomy of southern South American species of the wolf spider genus Allocosa (Araneae: Lycosidae: Allocosinae). 1 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 2 records from Happywhale - Long-finned Pilot Whale in Southern Ocean. 84122 records from Happywhale - Humpback Whale in North Pacific Ocean. 1 records from The Japanese species of the genus Gracilentulus (Protura: Acerentomidae). 21 records from Demosponges of the genus Hymedesmia (Poecilosclerida: Hymedesmidae) from Rathlin Island, Northern Ireland, with a description of six new species. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 2 records from Chrysobothris bimaculata (Coleoptera: Buprestidae), a new species from Jamaica, with a key to the genus in Jamaica. 1 records from A new genus of Hoplojassini from French Guiana (Hemiptera: Cicadellidae Iassinae) and identification key for species of tribe. 82017124 records from Artportalen (Swedish Species Observation System). 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. IV. Alopoglossidae, Gymnophthalmidae. 1 records from Taxonomy of the ant genus Nesomyrmex Wheeler (Formicidae, Myrmicinae) in the Afrotropical region, with a review of current species groups and description of a new species of the N. angulatus group from Mozambique. 3 records from Contribution to the genus Anomala Samouelle, 1819 (Coleoptera: Scarabaeidae Rutelinae) of China and adjacent regions. Part I: descriptions of two new species and remarks on four species. 1 records from Description of a new genus and species of the subfamily Arcoscalpellinae Zevina, 1978 (Cirripedia: Thoracica: Scalpellidae) from deep waters of the South China Sea. 12 records from A new species of Hypostomus Lacépède, 1803 (Siluriformes: Loricariidae) from the rio Tocantins-Araguaia basin, Brazil. 1166 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 413272 records from DATAVES. 8 records from Revision of the genus Mniophila S, 1831 (Coleoptera: Chrysomelidae). 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 3 records from Supplementary Illustrations For Two Nemoura (Plecoptera: Nemouridae) Species. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 1 records from Discovery of Lymantini weevils (Coleoptera: Curculionidae: Molytinae) outside the Americas: Devernodes, a new genus for five new species from Southeast Asia. 4 records from Pterophoridae (Lepidoptera) fauna of the Republic of Tuva. 1 records from Glyptotermes chiraharitae n. sp., a new dampwood termite species (Isoptera: Kalotermitidae) from India. 41 records from NEON Biorepository Zooplankton Collection (DNA Extracts). 11 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 482 records from Pez León en Venezuela. 4 records from Morphology and phylogeny of scalopine moles (Eulipotyphla: Talpidae: Scalopini) from the eastern Himalayas, with descriptions of a new genus and species. 41 records from The cicadas (Hemiptera: Cicadidae) of Peru including the description of twenty-four new species, three new synonymies, and thirty-seven new records. 1874 records from Happywhale - Humpback Whale in Arctic Ocean. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 7 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 193 records from The diversity of the genus Aricidea (Polychaeta: Paraonidae) from the Sea of Marmara, with descriptions of two new species and two new records for the Mediterranean fauna. 10 records from Overlooked diversity in African Solanum (Solanaceae): new and endangered Solanum agnewiorum from Kenya. 1 records from Coelogynopora schockaerti n. sp. (Proseriata: Coelogynoporidae), a remnant of a platyhelminth coldwater fauna in the northwestern Mediterranean?. 83803 records from Florida Keys Reef Visual Census 2014. 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 1 records from Amage imajimai sp. nov., a new species of Ampharetidae (Annelida: Polychaeta) from Japanese waters. 1 records from Chilopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Revision of Tynacantha Dallas with description of two new species (Hemiptera: Heteroptera: Pentatomidae: Asopinae). 25 records from Notes on Mediterranean Theridiidae (Araneae) – II. 28 records from Happywhale - Long-finned Pilot Whale in North Atlantic Ocean. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 1 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 16 records from Five new species of freshwater crabs of the genera Ghatiana Pati & Sharma, 2014 and Sahyadriana Pati & Thackeray, 2018 from India (Decapoda: Brachyura: Gecarcinucidae). 6 records from Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae). 1 records from Description and bioecology of two new species of the genus Cryncus (Orthoptera Gryllidae, Gryllinae) from Cameroon with a key and distribution map of all African species. 13 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 1 records from A new acotylean flatworm, Armatoplana colombiana n. sp. (Platyhelminthes: Polycladida: Stylochoplanidae) from the Caribbean coast of Colombia, South America. 2 records from Megaluropidae *. 1 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 44 records from Three new species and two new records of the genus Cotesia Cameron (Hymenoptera: Braconidae) from Iran. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 1 records from A new species of Hippopsis Lepeletier & Audinet-Serville, 1825 from Panama and key to species (Coleoptera, Cerambycidae, Lamiinae). 1 records from A New Quadrannulate Species of Orobdella (Hirudinida: Arhynchobdellida: Orobdellidae) from Kii Peninsula, Japan. 5 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 9 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 2 records from First report of the spider genus Desis (Araneae, Desidae) from China, with description of a new species. 5 records from New Species Of Neoperla Needham And Phanoperla Banks (Plecoptera: Perlidae) From The Philippine Islands. 6 records from Two new species of Selitrichodes (Hymenoptera: Eulophidae: Tetrastichinae) inducing galls on Casuarina (Casuarinaceae). 10 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 4 records from A new species Cyrtodactytlus Gray (Squamata: Gekkonidae) from western Thailand and the phylogenetic placement of C. inthanon and C. doisuthep. 184 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 2 records from Water striders (Heteroptera: Gerromorpha: Gerridae) of Romania with an update on the distribution of Gerris gibbifer and G. maculatus in southeastern Europe. 12 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 1 records from Craspedorrhynchus linardii, a new species of chewing louse (Phthiraptera: Ischnocera: Philopteridae) from the Gray-headed Kite (Aves: Falconiformes: Accipitridae). 76008 records from Field Museum of Natural History (Botany) Fungi Collection. 6 records from Review of the North American fauna of Drymeia Meigen (Diptera, Muscidae) and evaluation of DNA barcodes for species-level identification in the genus. 6 records from Review of the moray eels (Anguilliformes: Muraenidae) of the Red Sea, with description of a new species. 2 records from A new species of Campylocia Needham & Murphy, 1924 (Ephemeroptera, Euthyplociidae) from Northern Brazil. 20 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 2 records from Description of a new species of Cosmocerca Diesing, 1861 (Nematoda Cosmocercidae) in Hoplobatrachus crassus (Jerdon, 1853) (Anura: Dicroglossidae from Asansol coal-field area, West Bengal, India. 39 records from Huangilene, a new genus for the Miltochrista alikangiae (Strand, 1917) species-group, with descriptions of three new species from Indochina, continental China and Taiwan (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 20 records from A new genus and five new species of Neocoelidiinae leafhoppers from Brazil (Insecta: Hemiptera: Cicadellidae) with a key to males. 17 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 2 records from New taxa of extant and fossil primitive moths in South-East Asia and their biogeographic significance (Lepidoptera, Micropterigidae, Agathiphagidae, Lophocoronidae). 7 records from Pilargidae (Annelida: Phyllodocida) from coastal and deep waters of the Southwestern Atlantic, with descriptions of two new species. 4016 records from The Purdue Entomological Research Collection. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 1 records from The third South American species of the genus Pectenobunus Roewer, with a new synonymy for the genus (Opiliones, Eupnoi, Sclerosomatidae, Gagrellinae). 22 records from New species of the orb-weaving spider genus Chrysometa (Araneae, Tetragnathidae) from oak forests near of the Pico de Orizaba National Park (Veracruz, Mexico). 147 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 5 records from Three new brackish-water thalassocypridine species (Crustacea: Ostracoda: Paracyprididae) from the Ryukyu Islands, southwestern Japan. 19 records from Unraveling the white-clothed Diestostemma Amyot & Serville: a taxonomic revision of the American sharpshooters of the D. bituberculatum complex (Hemiptera: Cicadellidae). 1 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 13 records from Four new species of Phrynus, Lamarck (Arachnida: Amblypygi) from Mexico. 28 records from Scorpions of the Horn of Africa (Arachnida Scorpiones) Part XXIII Buthus (Buthidae), with description of two new species. 272 records from Plants galls. 2 records from Description and taxonomic analysis of a tuberculated turtle leech from the Outer Banks, North Carolina, USA, provisionally identified as Placobdella multilineata Moore, 1953 (Hirudinea: Glossiphoniidae). 370 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2007. 42195 records from DMNH Birds. 2 records from Two new species of Centaurea sect. Microlophus (Asteraceae, Cardueae) from Iran. 419 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 1 records from Happywhale - Long-finned Pilot Whale in Arctic Ocean. 130 records from The millipede genus Leucogeorgia Verhoeff, 1930 in the Caucasus, with descriptions of eleven new species, erection of a new monotypic genus and notes on the tribe Leucogeorgiini (Diplopoda: Julida: Julidae). 42 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 3 records from A new madicolous species of Nilotanypus Kieffer (Diptera: Chironomidae) from Amazon region, northwestern Brazil. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 5 records from First record of the genus Tanaostigma (Hymenopteraı Chalcidoideaı Tanaostigmatidae) from the Afrotropical region with description of three new species. 2 records from New species of Silhouettea (Teleostei: Gobiidae) from Qeshm Island, Iran and the DNA barcoding of the Persian Gulf and Oman Sea gobies. 140 records from Collection Gilles Becquet (BOUM). 2 records from Notes on species of the genus Chlaenius Bonelli, 1810 (Coleoptera: Carabidae, Chlaeniini) from four agro-climatic zones of Rajasthan, with description of two new species. 3 records from Taxonomic revision of the Mexican Eucyclops (Copepoda: Cyclopoida) with comments on the biogeography of the genus. 18 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 1 records from Sarcocheilichthys vittatus, a new species of gudgeon (Teleostei: Cyprinidae) from the Poyang Lake Basin in Jiangxi Province, South China. 2 records from Validity of Psammoperca datnioides Richardson 1848 and redescriptions of P. waigiensis Cuvier in Cuvier & Valenciennes 1828 and Hypopterus macropterus (Günther 1859) in the family Latidae (Perciformes) from the Indo-West Pacific. 9042 records from Northern Biodiversity Program Coleoptera (2010-2011). 4 records from An annotated and illustrated checklist of the Indian cuckoo wasps (Hymenoptera: Chrysididae). 6 records from Taxonomic Notes On Guaranyperla (Plecoptera: Gripopterygidae). 1 records from New records of Synallactes virgulasolida Massin & Hendrickx, 2010 (Echinodermata: Holothuroidea) from the eastern Pacific. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 11 records from Systematic notes on some leptomedusa species with a description of Neotima galeai n. spec. (Hydrozoa, Cnidaria). 1156 records from Happywhale - Humpback Whale in Indian Ocean. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 2 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 1 records from Litsea dorsalicana (Lauraceae): a new species from limestone areas in northern Guangxi, China. 5 records from Neotropical osmylids (Neuroptera, Osmylidae): Three new species of Isostenosmylus Krüger, 1913, new distributional records, redescriptions, checklist and key for the Neotropical species. 5 records from Description of the lucky Cophyla (Microhylidae, Cophylinae), a new arboreal frog from Marojejy National Park in north-eastern Madagascar. 8 records from The fishery ground near Alexandria. XX. Nemertini by Herman Friedrich (1940).Notes and Memoirs No 38.. 2 records from Happywhale - Mediterranean Monk Seal in North Atlantic Ocean. 1171 records from Glasaalmigratie - Glass eel migration in the river Yser. 37 records from Happywhale - Short-beaked Common Dolphin in North Pacific Ocean. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 25 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 14 records from Kosrae Invasive Database. 7 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 10 records from New species of Pseudoscorpiones (Arachnida) from tree hollows in a Mediterranean oak forest in Spain. 3 records from Rediscovery and redescription of a deep-sea shrimp Lebbeus longidactylus (Kobjakova, 1936) (Crustacea: Decapoda: Caridea: Thoridae) based on material from the Nemuro Strait, southwestern Sea of Okhotsk. 3 records from Oxynoemacheilus shehabi, a new nemacheilid loach from the upper Orontes in southern Syria (Teleostei: Nemacheilidae). 1 records from Phliantidae *. 87 records from Guasuctenus gen. nov., a new Neotropical spider genus of Ctenidae (Araneae). 2 records from Transfer of two South American ant species from Tapinoma Foerster 1850 to Forelius Emery 1888 (Hymenoptera: Formicidae: Dolichoderinae). 50 records from Amphibians (Amphibia, Anura and Caudata) and reptiles (Reptilia, Squamata) from the headwaters of Río Guázaro on the Caribbean versant of Veraguas province, western Panama. 3 records from Description of two new species of Seinura Fuchs, 1931 (Nematoda: Aphelenchoididae) from Iran. 1 records from Description of the adult and larva of Clunio balticus Heimbach, 1978 (Diptera Chironomidae) from the seashore of Bergen (Norway). 2 records from First record of the genus Microtityus Kjellesvig-Waering, 1966, from Puerto Rico, with description of two new species (Scorpiones: Buthidae). 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 4 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 22 records from Description of Bagarius vegrandis, a new species of sisorid catfish from Indochina (Actinopterygii: Siluriformes), with notes on the identity of Bagarius bagarius. 2960 records from Weber State University Herbarium. 4 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 11 records from An annotated checklist of the Iranian Brentidae (Coleoptera: Curculionoidea). 9 records from Happywhale - Peale's Dolphin in South Atlantic Ocean. 2 records from New record of the steppe longhorn beetle species Phytoecia (Musaria) argus (G. F. Frölich, 1793) (Cerambycidae: Lamiinae) in Bulgaria. 2 records from An interesting new species of Kamimuria (Plecoptera: Perlidae) from China, with notes on K. grandispinata Du & Sun. 553 records from Molecular phylogeny of the genus Lasiopogon (Diptera: Asilidae) and a taxonomic revision of the bivittatus section. 6 records from Correctly mating: on the actual female of Hibana talmina Brescovit and the description of H. labonita sp. n. (Araneae, Anyphaenidae). 2 records from A New Abdominally Parasitizing Bopyrid, Anisarthrus okunoi sp. nov. (Crustacea: Isopoda), Infesting the Hinge-Beak Shrimp Rhynchocinetes uritai Kubo, 1942 (Crustacea: Decapoda: Rhynchocinetidae). 1102 records from Plantas laguna El Tinije. 29 records from Genera of the Asian Catfish Families Sisoridae and Erethistidae (Teleostei: Siluriformes).. 60 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 18 records from Happywhale - Fin Whale in Arctic Ocean. 6 records from Transfer of the Namibian Argistes africanus Simon, 1910 (Araneae: Liocranidae) to Afroceto Lyle & Haddad, 2010 (Trachelidae), with a new synonym. 81 records from Kystfuruskoger i Tysnes og Fusa. 29 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 4 records from Two new species of the armored spider genus Tetrablemma O. P. - Cambridge, 1873 from northern South America (Araneae: Synspermiata: Tetrablemmidae). 10 records from A new species of the spider genus Wirada (Araneae, Theridiidae) from Mexico, with taxonomic notes on the genus and a key to the species. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 1 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 11 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanteriidae).. 3 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 2 records from Nothogreniera new genus, for two species of Australian " Paracnephia " (Diptera: Simuliidae). 2 records from A new species and depth record of bopyrid (Crustacea, Isopoda) from a squat lobster in the Kuril-Kamchatka Trench. 197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 445 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 1 records from Description of a new species of the Melanorivulus pictus species-group (Cyprinodontiformes: Rivulidae) from the Rio Paraná basin in Brazil. 3 records from First records of Edwardsiana sociabilis (Ossiannilsson, 1936) and Laburrus pellax (Horváth, 1903) (Hemiptera, Auchenorrhyncha: Cicadellidae) in Switzerland. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 8 records from New species and records of Paraphloeostiba Steel, 1960 from China and Laos and descriptions of four new species of related genera (Coleoptera: Staphylinidae Omaliinae: Omaliini). 3 records from Bodotria paraspinifera sp. nov. (Crustacea: Cumacea: Bodotriidae), a new Korean cumacean. 1 records from Larval And Egg Morphology Of Paraperla Frontalis (Banks, 1902) And P. Wilsoni Ricker, 1965 (Plecoptera: Chloroperlidae). 1 records from Taxonomic novelties in Apocynaceae subfam. Asclepiadoideae from New Caledonia. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 20 records from 2020_nsmk_smpl_mm. 2 records from Two new species of Austrotinodes Schmid (Insecta, Trichoptera, Ecnomidae) from southeastern Brazil. 140 records from Naturalis Biodiversity Center (NL) - Diptera. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 3 records from Rediscovery of a fossil dolichoderine ant lineage (Hymenoptera: Formicidae: Dolichoderinae) and a description of a new genus from South America.. 1 records from Trachyuropodid mites (Acari: Uropodina) from South-East Asia: catalog, new key and description of two new species. 4 records from Happywhale - Striped Dolphin in North Atlantic Ocean. 10 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 1 records from A new aquatic beetle family, Meruidae, from Venezuela (Coleoptera: Adephaga). 11 records from Grewia hispidissima Wahlert, Phillipson & Mabb., sp. nov. (Malvaceae, Grewioideae): a new species of restricted range from northwestern Madagascar. 43 records from Taxonomic revision of Guapinannus Wygodzinsky, 1951 (Hemiptera: Schizopteridae), with description of 19 new species. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 2 records from Neue Oribatiden (Acari) aus Deutschland III. Suctobelba carcharodon n. sp. und Suctobelba prominens n. sp.. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 30 records from Validity of Platycephalus grandispinis Cuvier, 1829, with Priority over Platycephalus longispinis Macleay, 1884 (Actinopterygii: Scorpaeniformes: Platycephalidae). 3 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 23 records from Six new species of Orthochirus Karsch, 1892 from Iran (Scorpiones Buthidae). 13 records from Yuelushannus gen. nov. (Araneae, Linyphiidae) from China. 4 records from Urohaustoriidae *. 14 records from On three new oonopid species from China and the discovery of the male Orchestina bialata Liu, Xiao & Xu, 2016 (Araneae: Oonopidae). 5 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 38 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 3 records from Vasopora ceramica n. gen., n. sp. - a new abyssal cyclostome bryozoan from polymetallic nodules in the Russian exploration area, Clarion-Clipperton Fracture Zone, eastern Pacific Ocean. 214406 records from University of Minnesota Insect Collection. 3 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas I. Zwei neue Arten der Gattung Suctobelba Paoli aus der Oberlausitz (DDR): Suctobelba scalpellata n. sp. und Suctobelba secta n. sp.. 5 records from A review of the stink bug genus Plautia Stål from Japan (Hemiptera, Heteroptera, Pentatomidae). 8 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 8 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 1 records from Cryptotermes camelus (Isoptera: Kalotermitidae), a new drywood termite species from the Bolivian Chaco. 189 records from UCM Vertebrate Observations Collection (Arctos). 5 records from Agrostis barikii (Poaceae: Agrostidinae), a new grass species from Western Himalaya, India. 1 records from Laubuka parafasciata, a new cyprinid fish species (Teleostei: Cyprinidae) from Mizoram northeastern India. 15 records from Revision of Ganomymar De Santis, 1972, a remarkable genus of Mymaridae (Hymenoptera, Chalcidoidea) from Madagascar. 60962 records from MLZ Bird Collection (Arctos). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 1 records from Description of Malenchus gilanensis n. sp. from Iran. 5 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 14 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 1 records from Two new species of freshwater, cave-dwelling crabs of the genus Neostrengeria Pretzmann, 1965, from Colombia (Crustacea: Decapoda: Pseudothelphusidae). 5 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 1 records from Pseudoscopas carbonelli n. sp. (Orthoptera: Acrididae: Melanoplinae) from southern Brazil, including chromosome complement. 4 records from A new small-sized Theloderma (Anura: Rhacophoridae) from Laos. 2592 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 5 records from Two new species of Aulospongus Norman, 1878 with a key to the Atlantic species (Poecilosclerida; Demospongiae; Porifera). 125 records from A revision of Rhodomantis Giglio-Tos, 1917 (Mantodea: Mantidae: Mantinae). 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 1 records from Tazarcus, a new phylogenetically unplaced genus of two flightless weevils with metapleural ridge from the Eastern Arc Mountains, Tanzania (Coleoptera: Curculionidae: Molytinae). 7 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). I. Gracilipalpe, morchella and nigrum groups. 385 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 7 records from Happywhale - Leatherback Sea Turtle in North Pacific Ocean. 207 records from NEON Biorepository Zooplankton Collection (Remaining Bulk Taxonomy Sample). 4 records from A remarkable new species of Micropeza Meigen (Diptera: Micropezidae) from Caatinga biome, Brazil. 324 records from MICA - Muskrat occurrences collected by RATO in East Flanders, Belgium. 1 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 2 records from First record of the Cyrtodactylus brevipalmatus group (Squamata: Gekkonidae) from Vietnam with description of a new species. 6 records from Unexpected discovery of six new species of Aphyosemion (Cyprinodontiformes, Aplocheilidae) in the Wonga-Wongué Presidential Reserve in Gabon. 1 records from Deep-sea Ophiuroidea (Echinodermata) from the Danish Galathea II Expedition 1950 - 52, with taxonomic revisions. 5 records from Redescription of the poorly known crab spider Xysticus spasskyi (Araneae: Thomisidae). 1 records from A redescription of Moina australiensis Sars, 1896 (Cladocera: Moinidae) with short notes on Australian moinids. 1 records from The bees of Lebanon (Hymenoptera: Apoidea: Anthophila). 18 records from Three new generic records and descriptions of four new species of jumping spiders (Araneae, Salticidae) from Sri Lanka. 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 1 records from On a new species of Euchondrus Boettger, 1883 from Syria (Pulmonata: Enidae). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 71 records from Revision of Brada Stimpson, 1853, and Bradabyssa Hartman, 1967 (Annelida, Flabelligeridae). 11 records from A New Perlodes Species And Its Subspecies From The Balkan Peninsula (Plecoptera: Perlodidae). 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 1 records from A new deepwater species of Calliopiidae, Halirages helgae (Crustacea, Amphipoda), with a synoptic table to Halirages species from the northeast Atlantic. 2 records from Four new species of Goloboffia (Mygalomorphae: Migidae) from Chile. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 1 records from A new species of Lithophane Hbn. (Lepidoptera, Noctuidae, Xyleninae). 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 30 records from On the origin and diversification of the stygobiotic freshwater snail genus Hauffenia (Caenogastropoda: Hydrobiidae) with special focus on the northern species and the description of two new species. 9 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 367 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 21097 records from sarce_rockyshores. 2 records from Additions to the millipede family Caseyidae. II. Martenseya, a new genus of miniature, blind millipedes from California (Diplopoda, Chordeumatida Striariidea, Striarioidea, Caseyidae). 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 8 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 88 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 20696 records from Herbier Louis-Marie (QFA) - Collection de lichens. 2 records from Morphology and molecules say: Tanytarsus latens, sp. nov. from Finland (Diptera: Chironomidae). 3 records from A new genus and species of natricine snake from northeast India. 11 records from Revisions of two poorly known species of Opisthotropis Günther, 1872 (Squamata: Colubridae: Natricinae) with description of a new species from China. 4 records from Two new cryptic species of Isometrus (Scorpiones Buthidae) from the northern Western Ghats India. 1 records from A new Rhopalomeris species (Diplopoda: Glomerida: Glomeridae), and notes on the phylogenetic relationships between glomeridans in Vietnam. 26 records from Chaoborus flavicans Meigen (Diptera, Chaoboridae) is a complex of lake and pond dwelling species: a revision. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 12 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 6 records from The crane fly genus Libnotes Westwood, 1876 (Diptera: Limoniidae) for Korea including two new species and an identification key. 1 records from A new subterranean Maraenobiotus (Crustacea: Copepoda) from Slovenia challenges the concept of polymorphic and widely distributed harpacticoids. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 2 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 5 records from Night stalkers from above: A monograph of Toxicodryas tree snakes (Squamata Colubridae) with descriptions of two new cryptic species from Central Africa. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 4 records from Adventive Staphylinidae (Coleoptera) of the Maritime Provinces of Canada: further contributions. 1 records from The first hygropetric Platynectes and its larva from eastern China (Coleoptera: Dytiscidae). 9 records from The first data on species diversity of leeches (Hirudinea) in the Irtysh River Basin, East Kazakhstan. 1 records from Eight species in the Nebela collaris complex: Nebela gimlii (Arcellinida, Hyalospheniidae), a new species described from a Swiss raised bog. 1 records from Record of a new species of the genus Viridopromontorius Luna de Carvalho (Strepsiptera: Corioxenidae) from India with a revised key to Corioxenidae. 4127 records from University of Alberta Freshwater Invertebrate Collection (UAFIC). 1 records from A New Subspecies Of Chrysolina Sanguineocincta (Crotch, 1871) From Turkey (Coleoptera: Chrysomelidae: Chrysomelinae). 1 records from Diaparsis phobos sp. nov. and D. deimos sp. nov., two amazing new species of Tersilochinae (Hymenoptera: Ichneumonidae) from Madagascar. 1 records from Happywhale - Layard's beaked whale in Southern Ocean. 10 records from A new genus and species of Haplobainosomatidae (Diplopoda: Chordeumatida) from the MSS of the Sierra de Guadarrama National Park, central Spain. 52 records from Palaearctic Osmia bees of the subgenera Hemiosmia, Tergosmia and Erythrosmia (Megachilidae, Osmiini): biology, taxonomy and key to species. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 10 records from An inordinate fondness for Osedax (Siboglinidae: Annelida): Fourteen new species of bone worms from California. 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 179 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 1 records from A new cave-dwelling Gekko (Gekko) from Lopburi Province, central Thailand (Squamata, Gekkonidae). 13 records from Exoasota pursatensis Ko & Bae, new genus and species of the Spilomelinae (Lepidoptera: Pyraloidea: Crambidae) from Indochina. 12 records from A mountain of millipedes I: An endemic species-group of the genus Chaleponcus Attems, 1914, from the Udzungwa Mountains, Tanzania (Diplopoda, Spirostreptida, Odontopygidae). 8 records from The millipede genus Tylopus Jeekel, 1968 (Diplopoda, Polydesmida, Paradoxosomatidae), with a key and descriptions of eight new species from Indochina. 750 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2013. 5 records from A new Candonopsini (Ostracoda) genus from subterranean waters of New South Wales (Australia). 2517 records from Freshwater fishes of Greece. 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 3 records from Otacilia fansipan spec. nov., the second congener recorded from Vietnam (Arachnida: Araneae: Phrurolithidae). 126 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 1 records from A new species of Liphistius from Myanmar and description of the actual male of L. birmanicus Thorell, 1897 (Araneae, Mesothelae, Liphistiidae). 2 records from A remarkable new plant bug genus and species (Hemiptera, Heteroptera, Miridae, Deraocorinae) from the Australian wet tropics. 11 records from Revision of Aciuroides Hendel and Neoacanthoneura Hendel (Diptera: Ulidiidae: Pterocallini). 5 records from Rhinogobius houheensis, a new species of freshwater goby (Teleostei: Gobiidae) from the Houhe National Nature Reserve, Hubei province, China. 1 records from New Antarctic stenothoids sensu lato (Amphipoda, Crustacea). 1 records from Gymnesigobius medits (Teleostei: Gobiidae), a new gobiid genus and species from the western Mediterranean slope bottoms. 3137 records from Salvatore S. Anzaldo Collection. 1876 records from NMU Mammal Collection (Arctos). 14 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 5 records from Heteragrion lencionii (Odonata: Heteragrionidae) sp. nov. from Serra de Itabaiana National Park, Northeastern Brazil. 3 records from Species diversity of Rhinebothrium Linton, 1890 (Eucestoda: Rhinebothriidea) from Styracura (Myliobatiformes: Potamotrygonidae), including the description of a new species. 8 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 3 records from A new genus and species of Sclerodactylidae (Echinodermata: Holothuroidea: Sclerothyoninae) from the Pacific coast of Panama, and assignment of Neopentamera anexigua to Sclerothyoninae. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 32 records from A new tanaidacean subfamily, Bathytanaidinae (Crustacea: Paratanaididae), from the Australian continental shelf and slope. 24 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 22 records from Contributions to the study of the grasshopper (Orthoptera: Acrididae Gomphocerinae) courtship songs from Kazakhstan and adjacent territories. 85 records from The Crematogaster (Hymenoptera, Formicidae, Myrmicinae) of Costa Rica.. 3 records from Aretopsis sandybrucei, a new deep-water shrimp (Malacostraca: Decapoda: Caridea: Alpheidae) from the Coral Sea. 165 records from CMNH Mammals. 170 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 1 records from Afroanomalia pseudoclistopyga, a new genus and species of pimpline parasitoid wasp (Hymenoptera: Ichneumonidae: Pimplinae) from the Afrotropical region. 4 records from Primulina jiangyongensis (Gesneriaceae), a new species from Southern Hunan, China. 1 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 2 records from Macrozoque hoplandrioides (Coleoptera: Staphylinidae: Aleocharinae), a new genus and species of false Lomechusini from México. 25 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 16 records from Three new species of earthworms belonging to the genera Amynthas and Metaphire (Oligochaeta: Megascolecidae) from Yunnanı China. 1 records from Species of Wadicosa (Araneae, Lycosidae): a new species close to W. quadrifera (Gravely) from the Western Ghats, India. 14 records from New host-plants records of Afrotropical Gelechiidae (Lepidoptera), with description of three new species. 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 16 records from Review of the Poecilimon (Poecilimon) zonatus species group and description of new species from Turkey with data on bioacoustics and morphology (Orthoptera: Phaneropterinae). 3 records from A revision of the New Zealand weevil genus Irenimus Pascoe, 1876 (Coleoptera: Curculionidae: Entiminae). 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 8 records from Four new species of Diptilomiopinae from China (Acari: Eriophyoidea: Diptilomiopidae). 3 records from The genus Thelepus Leuckart, 1849 (Annelida, Thelepodidae) in Brazil, with a redescription of the holotype of T. setosus (Quatrefages, 1866). 1 records from Rediscovery of Terebratulina austroamericana Zezina, 1981 (Brachiopoda: Cancellothyrididae) from off northern Chile. 1 records from A new diminutive sisorid catfish (Actinopterygii: Siluriformes) from northeastern India. 12 records from Happywhale - Beluga in Arctic Ocean. 10 records from Three species of Reteporella (Bryozoa: Cheilostomata) in a diapiric and mud volcano field of the Gulf of Cádiz, with the description of Reteporella victori n. sp. 27 records from Revisionary systematics of the endemic soft coral fauna (Octocorallia: Alcyonacea: Alcyoniina) of the Agulhas Bioregion, South Africa. 5 records from Halanonchus scintillatulus sp. nov. from New Zealand and a review of the suborder Trefusiina (Nematoda: Enoplida). 4 records from Additional knowledge respecting taxonomy of the social wasp genus Ropalidia (Hymenoptera: Vespidae: Polistinae) from Vietnam, with new records of three species and an updated key to species. 1 records from A new species and southernmost record of Cestrus Townes (Hymenoptera Ichneumonidae, Cryptinae). 2 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 4 records from New records of phytoseiid mites from Mauritius Island (Acari: Mesostigmata. 4 records from The ant genus Tetraponera in the Afrotropical region: the T. grandidieri group (Hymenoptera: Formicidae).. 5 records from Onosma satensis sp. nov. (Boraginaceae: Lithospermeae), a new species from Hakkari (eastern Anatolia, Turkey). 2 records from A new genus Microsarimodes with one species from Hainan Province in China (Hemiptera: Fulgoromorpha: Issidae). 47 records from Rare, deep-water and similar: revision of Sibogasyrinx (Conoidea: Cochlespiridae). 3 records from Onuphi s and Mooreonuphis (Annelida: Onuphidae) from West Africa with the description of three new species and the reinstatement of O. landanaensis Augener, 1918. 7 records from Sechelleptus arborivagus sp. nov., a new arboreal spirostreptid millipede (Diplopoda, Spirostreptidae) endemic to Mayotte Island (Comoros Archipelago), Indian Ocean. 63085 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 1995 records from Monitoreo y morfometría de la avifauna de la Universidad del Valle 2011-2012. 2 records from New and interesting palpigrades (Arachnida, Palpigradi) of the genera Koeneniodes Silvestri, 1913 and Prokoenenia Börner, 1901 from Asia. 3 records from Dichromatobolus, a new genus of spirobolidan millipedes from Madagascar (Spirobolida, Pachybolidae). 2 records from Sinopyrophorinae, a new subfamily of Elateridae (Coleoptera, Elateroidea) with the first record of a luminous click beetle in Asia and evidence for multiple origins of bioluminescence in Elateridae. 9 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 3 records from Two new species of lotic breeding salamanders (Amphibia, Caudata, Hynobiidae) from western Japan. 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 1 records from A new edible cricket species from Africa of the genus Scapsipedus. 1573 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 1 records from On the taxonomic status of Asthenodipsas vertebralis (Boulenger, 1900) (Squamata Pareidae) in Borneo with the description of a new species. 47 records from Re-classification of Lycoriella Frey sensu lato (Diptera, Sciaridae), with description of Trichocoelina gen. n. and twenty new species. 1 records from A revision of the genus Hypotrix Guenee in North America with descriptions of four new species and a new genus (Lepidoptera, Noctuidae, Noctuinae, Eriopygini). 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 2 records from SyNoeca ilheeNsis sp. nov., a new social wasp (Hymenoptera, Vespidae, Polistinae) from Brazilian lowland Atlantic Forest. 29 records from New species, synonymy and records of Endomia and Stenidius (Coleoptera: Anthicidae) from Asia. 2 records from Designation Of A Replacement Name For Capnioneura Veronicae Nomen Nudum (Capniidae Plecoptera). 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 1 records from Three endemic Aphaenogaster from the Siculo-Maltese archipelago and the Italian Peninsula: part of a hitherto unrecognized species group from the Maghreb? (Hymenoptera: Formicidae: Myrmicinae). 41 records from MSUM Ichthyology and Herpetology Collections. 9 records from On some deep-sea Stenheliinae from the Gulf of California and the west coast of the Baja California Peninsula (Mexico): the genus Delavalia Brady, 1869 and proposal of Archaeohuysia gen. nov. and Diarthropodella gen. nov. (Copepoda Harpacticoida: Miraciidae). 3 records from Epiproct And Dorsal Process Structure In The Allocapnia Forbesi Frison, A. Pygmaea (Burmeister), And A. Rickeri Frison Species Groups (Plecoptera: Capniidae), And Inclusion Of A. Minima (Newport) In A New Species Group. 4 records from The fossil avifauna of the tar seeps Las Breas de San Felipe, Matanzas, Cuba. 4 records from Two new species of Psephenops Grouvelle (Coleoptera: Byrrhoidea: Psephenidae) from Panama. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 22 records from New insights into polyphyly of the harpacticoid genus Delavalia (Crustacea, Copepoda) through morphological and molecular study of an unprecedented diversity of sympatric species in a small South Korean bay. 4 records from Seven species of Pseudopecoeloides Yamaguti, 1940 (Digenea, Opecoelidae) from temperate marine fishes of Australia, including five new species. 75 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 2 records from The first record of the genus Desertoniscus Verhoeff, 1930 (Isopoda, Oniscidea, Agnaridae) from Europe, with the description of a new species. 42 records from Twenty new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental Region. 2 records from Description of the female and egg of Phantasca phantasma (Westwood, 1859) (Phasmatodea: Diapheromeridae: Diapheromerinae). 1 records from Notes on west Palaearctic species of the genus Trigonurus Mulsant, 1847 (Coleoptera: Staphylinidae: Trigonurinae). 9 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 2 records from Two new species of the genus Malayepipona Giordani Soika (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with updated key to all recognised species. 1 records from A new species of Aphelocheirus (Hemiptera: Heteroptera: Aphelocheiridae) from Morocco. 24 records from Happywhale - Risso's Dolphin in North Atlantic Ocean. 8 records from Two new species and records of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae) from southeastern China. 1 records from Thraulodes marianoi sp. nov., a remarkable new species of mayfly (Ephemeroptera Leptophlebiidae) with dark wings from the southern Brazilian Atlantic Forest. 1 records from Redescription of three species of Apobaetis Day, 1955 (Ephemeroptera: Baetidae). 2 records from The dark side of pumpkin toadlet: a new species of Brachycephalus (Anura: Brachycephalidae) from Serra do Brigadeiro, southeastern Brazil. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 1 records from Tibetyrus gen. nov., a new myrmecophilous Tyrini from Xizang, China (Coleoptera: Staphylinidae: Pselaphinae). 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 5 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 286 records from California State University, Long Beach Birds. 1 records from A New Record From The Genus Callicera Panzer, 1809 (Insecta: Diptera: Syrphidae) From India. 4 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 1 records from Astragalus orientopersicus, sp. nov. (Fabaceae), a new taxon from the Khorassan province (Iran). 502 records from Happywhale - Leopard seal in Southern Ocean. 3 records from The eel genus Macrocephenchelys (Anguilliformes: Congridae) in Taiwan, with description of a new species. 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 3 records from Hurleyella, a new genus of Nearctic Dolichopodidae (Diptera). 2 records from Two new keratinophilic fungal species. 21 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 62 records from Characidium longum (Characiformes: Crenuchidae), a new fish from Venezuela.. 131 records from Some thecate hydroids (Cnidaria: Hydrozoa) from off New Caledonia collected during KANACONO and KANADEEP expeditions of the French Tropical Deep-Sea Benthos Program. 1 records from Taito adrik, a new harvestman species from the Área de Conservación Privada Panguana, Peruvian Amazonia (Opiliones: Laniatores: Cosmetidae). 13 records from Adding stars to the Chromodoris (Nudibranchia, Chromodorididae) galaxy with the description of four new species. 5 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 2 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 8 records from New species and records of Chasmogenus Sharp, 1882 from the southwestern margin of the Guiana Shield (Coleoptera: Hydrophilidae: Acidocerinae). 26 records from A new species of Tricorythodes Ulmer (Ephemeroptera: Leptohyphidae) from Uruguay. 2 records from Notes on Southeast Asian Stingless Bees of the Genus Tetragonula (Hymenoptera: Apidae), with the Description of a New Species from Thailand. 7 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 2 records from Rediscovery of Glenurus incalis Banks (Neuroptera: Myrmeleontidae), and notes on the Brazilian species of Glenurus Hagen. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 1696 records from Herbier National de Guinée (HNG). 1 records from Phylogenetic position of two Macrobiotus species with a revisional note on Macrobiotus sottilei Pilato, Kiosya, Lisi & Sabella, 2012 (Tardigrada: Eutardigrada Macrobiotidae). 49 records from Taxonomy of Central American water beetles in the genus Hydrochus Leach, 1817 (Coleoptera: Hydrochidae). 1 records from Out of the Neotropics: newly discovered relictual species sheds light on the biogeographical history of spider ants (Leptomyrmex, Dolichoderinae, Formicidae). 25 records from New records of Stenopygium Becker (Diptera: Dolichopodidae) from the Neotropical Region, and a key to species. 4479 records from Iowa State University Fishes Collection. 8 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 22114 records from Global compendium of Aedes albopictus occurrence. 1181501 records from Natural History Museum (London) Collection Specimens. 2 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 69 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 6 records from Notes on the genus Perittopus Fieber, 1860 (Hemiptera: Heteroptera: Veliidae with descriptions of three new species from Indochina. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 1 records from A new genus and new species assigned to Macrophthalmidae (Decapoda: Brachyura: Thoracotremata) from the Ryukyu Islands, Japan. 34 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 5 records from Six new and one known species of Geomonhystera (Nematoda, Monhysteridae) from moss, an epiphytic plant and soil in México and Ecuador. 572 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 35 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 3 records from Three new species of the subterranean genus Guiodytes from Guangxi, China (Coleoptera: Carabidae: Clivinini). 94 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 1433 records from Collection botanique Jaubert et Saul (BOUM). 31 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 3 records from Allocapnia Muskogee And A. Menawa, New Species Of Snowflies (Plecoptera: Capniidae) From The Talladega National Forest Region Of Eastern Alabama, U. S. A., Plus Four New State Records. 5 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 2 records from Two new species of Willowsia (Collembola: Entomobryidae) from Guizhou Province, China. 76 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 2 records from Two remarkable new species of oribatid mites (Acari: Oribatida) from Acacia litter of Kerala, India. 422108 records from NOAA AFSC North Pacific Groundfish Observer. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 1 records from A new sandstone-dwelling leaf-toed gecko (Gekkonidae: Dixonius mekongensis) from the Thai-Lao border. 8 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 2 records from Anisops sardeus Herrich-Schaeffer, 1849: first records from Hungary (Heteroptera: Notonectidae). 1 records from A New Genus and Species of Blind Sleeper (Teleostei: Eleotridae) from Oaxaca, Mexico: First Obligate Cave Gobiiform in the Western Hemisphere. 13 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) of Iran and adjacent territories. 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A new species of Xestophrys Redtenbacher, 1891 (Orthoptera: Tettigoniidae; Conocephalinae; Copiphorini) from India. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 4 records from Review the bamboo-feeding genus Arcofaciella Fennah, 1956 (Hemiptera: Fulgoromorpha: Delphacidae) with description of a new species from India. 1 records from New Species Of Apterobiroina L. Papp And Bentrovata Richards (Diptera, Sphaeroceridae) From Australia. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 37 records from Revision of the genus Platyscelis Latreille, 1818 from China (Coleoptera: Tenebrionidae: Platyscelidini). 14 records from Australian Marsh Beetles (Coleoptera: Scirtidae). 9. The relations of Australasian Ypsiloncyphon species to their Asian congeners, additions, mainly to Petrocyphon and Prionocyphon, and a key to Australian genera of Scirtinae. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 1 records from Acantorna-a new genus of Hymedesmiidae (Porifera, Demospongiae Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp.. 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 2 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 2 records from Early myriapodous arthropods from Australia: Maldybulakia from the Devonian of New South Wales. 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 4 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 14 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 27867 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 8 records from Three new species of Aricidea (Acmira) (Annelida: Paraonidae) from the Continental Shelf of Eastern Brazil, Southwestern Atlantic. 20 records from Three new species of the primitively segmented spiders from Mt Yuelu, Hunan, China (Mesothelae, Liphistiidae). 9 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 6 records from Potamotrygon boesemani (Chondrichthyes: Myliobatiformes: Potamotrygonidae), a new species of Neotropical freshwater stingray from Surinam. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 1 records from A new species of Smicromorpha (Hymenoptera, Chalcididae) from Vietnam, with notes on the host association of the genus. 1 records from The neotype designation for Podismopsis gynaemorpha Ikonnikov, 1911 (Orthoptera: Acrididae). 32 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 1 records from Happywhale - South American Sealion in South Atlantic Ocean. 138 records from A review of the Glossogobius giuris complex in Australia, with wider discussion on nomenclature and possible synonymies. 1 records from A new species of Dolichopoda (Orthoptera: Rhaphidophoridae; Dolichopodainae) from Western Greece. 71 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 16 records from The genus Syntozyga Lower (Lepidoptera, Tortricidae) in China, with descriptions of two new species. 74 records from New species of Sericini from Sri Lanka (Coleoptera, Scarabaeidae). 2 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 54 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 20 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 13 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 92 records from Review of the Australian Cyllodini (Coleoptera: Nitidulidae: Nitidulinae), with descriptions of new taxa, and notes on the genus Macleayania (Nitidulini). 10 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 564 records from Invasive Non-native species data in the Clyde catchment, collated by Central Scotland Forest Trust. 3 records from First record of the leafhopper tribe Adelungiini Baker (Hemiptera, Auchenorrhyncha, Cicadellidae: Megophthalminae) from Turkey, with notes on Achrus albicosta (Kusnezov, 1929). 15 records from Three new species of Miroculis from the Serra da Mocidade National Park, Roraima State, Brazil, with new records and checklist of the Leptophlebiidae (Ephemeroptera). 4 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 2 records from Dermaptera of Iran with description of Euborellia angustata sp. nov.. 1 records from Revision of the subgenus Nessus of the genus Hypocaccus from Central Europe, with description of a new species (Coleoptera: Histeridae). 3 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 6 records from Revision of the shore-fly genus Peltopsilopa Hendel (Diptera: Ephydridae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 1 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 1 records from First record of Orthelimaea himalayana (Ingrisch, 1990) (Orthoptera: Tettigoniidae: Phaneropterinae: Elimaeini) from India with description of its female. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1 records from Redescription of four species of Cytaea Keyserling, 1882 (Araneae: Salticidae). 2 records from New species of Simothraulopsis Demoulin, 1966 (Ephemeroptera: Leptophlebiidae) from Northeastern Region of Brazil. 1 records from A revision of the genus Bryolymnia Hampson in North America with descriptions of three new species (Lepidoptera, Noctuidae, Noctuinae, Elaphriini). 1045806 records from Belgian IFBL Flora Checklists (1939-1971). 138 records from New species of gall fly (Diptera: Fergusoninidae) from Eucalyptus camaldulensis (Myrtaceae) in southern Australia and its associated parasitoids and inquilines. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 21 records from New species and host plant records for Neotropical Rhagoletis Loew (Diptera: Tephritidae). 371 records from orthopteracollections-nhmj-ioj. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 10788 records from Collections of Bioclass, school #179, Moscow. 6 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 206 records from New Records of ground beetles for Colombia (Coleoptera: Carabidae). 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 2 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 34 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 2804 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 46 records from Brachymelecta Linsley, 1939, previously the rarest North American bee genus, was described from an aberrant specimen and is the senior synonym for Xeromelecta Linsley, 1939. 1 records from A new species of Acrotaphus Townes (Hymenoptera: Ichneumonidae: Pimplinae) from the Brazilian Amazon, with notes on its host spider behavioral modification. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 140 records from Revision of the morphology, phylogenetic relationships, behaviour and diversity of the Iberian and Italian ant-like Tachydromia Meigen, 1803 (Diptera: Hybotidae). 7 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 3 records from Dolichocaudus, a new genus in the leafhopper subfamily Evacanthinae (Hemiptera: Cicadellidae), with description of two new species. 31 records from Geographic structure of genetic variation in the Parachute Gecko Ptychozoon lionotum Annandale, 1905 across Indochina and Sundaland with descriptions of three new species. 5 records from Two new endemic species of Bistriopelma (Araneae: Theraphosidae) from Peru, including a new remarkable horned tarantula. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 2 records from Notes On Rhopalopsole Klapálek (Plecoptera: Leuctridae), With Descriptions Of Three New Species From Vietnam. 334 records from Hermit crabs of the genera Calcinus Dana, Clibanarius Dana, and Dardanus Paul’son from the PANGLAO 2004 Expedition, with description of a new species and a checklist of the hermit crabs of the Philippines (Crustacea: Anomura: Paguroidea). 5 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 18 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 9 records from New host and distribution records for Buprestidae (Coleoptera) from the state of Morelos, Mexico. 7 records from First record of the genus Agnara (Isopoda: Oniscidea) from Iran with descriptions of two new species. 25 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 1 records from Soil-inhabiting mites of the family Laelapidae (Acari: Mesostigmata) from Assiut Governorate, Egypt. 8 records from The Trichoptera of Panama. XII. Contributions to the family Glossosomatidae (Insecta: Trichoptera) in Panama. 3 records from Taxonomic revision of the Palaearctic Tetramorium chefketi species complex (Hymenoptera: Formicidae).. 2 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 2 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 16 records from Many things come in small packages: Revision of the clawless geckos (Crenadactylus: Diplodactylidae) of Australia. 8114 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 10 records from Meadow katydids (Orthoptera: Tettigoniidae: Conocephalini) from the Central-West Region of Brazil: Morphological, bioacoustic and cytogenetic study. 3 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 1 records from Additions to the taxonomy of the Afrotropical Tetramorium weitzeckeri species complex (Hymenoptera, Formicidae, Myrmicinae), with the description of a new species from Kenya. 3 records from ALLIUM (AMARYLLIDACEAE) SPECIES IN PAKISTAN: TWO NEW RECORDS AND A NEW SPECIES FROM ZHOB (BALOCHISTAN). 4 records from Happywhale - Bryde's whale in South Atlantic Ocean. 13 records from A revision of the spider genus Raveniola (Araneae, Nemesiidae). I. Species from Western Asia. 36 records from A review of Spathipheromyia (Diptera: Muscidae) from Argentina with the description of an extra-large new species. 49 records from Historical review, catalog of type specimens and online database of the ichthyology collection of the Instituto de Ciencias Naturales of the Universidad Nacional de Colombia (ICN-MHN). 5 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 2 records from The first species of the pseudoscorpion genus Lechytia Balzan, 1892 (Pseudoscorpiones, Chthoniidae) from New Zealand. 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 1051 records from BOEM Beaufort Sea, Alaska, Fish and Invertebrate Haul and Catch, with Oceanography, 2008. 2 records from A new species of the genus Mawenzhena Alexis & Delpont (Coleoptera Scarabaeidae: Cetoniinae: Goliathini) from South Korea. 4 records from A review of the feather mite family Gabuciniidae Gaud & Atyeo (Acariformes Astigmata: Pterolichoidea) of Brazil, with descriptions of eleven new species. 4 records from Four new earthworm species of Kazimierzus Plisko, 2006 (Clitellata, Kazimierzidae). 84 records from New Mexico Museum of Natural History and Science (NMMNHS) Insect specimens (Arctos). 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 7 records from A new genus and three new species of nemacheilid loaches from northern Irrawaddy drainage, Myanmar (Teleostei: Cypriniformes). 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 3 records from Two new species of the genus Tylostega Meyrick, 1894 (Lepidoptera: Crambidae) from China, with a list of all the known species in the world. 1 records from Erpetogomphus oxybelis sp. nov. from Veracruz, Mexico (Odonata: Gomphidae). 2 records from New fossil genus and new extant species of diatoms (Stephanodiscaceae, Bacillariophyceae) from Pleistocene sediments in the Neotropics (Guatemala, Central America): adaptation to a changing environment?. 1 records from Description of a new species of Megischus Brulle (Hymenoptera, Stephanidae), with a key to the species from China. 5 records from The species of the bee genus Centris of the “ hyptidis group ” revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 1 records from A new species of the genus Paratus Simon (Araneae: Liocranidae) from Thailand. 3 records from A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Tamil Nadu, Southern India. 454 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 6 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 5 records from On the new monotypic wolf spider genus Ovia gen. nov. (Araneae: Lycosidae, Lycosinae). 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 416 records from A taxonomic monograph of the genus Tylodinus Champion (Coleoptera: Curculionidae: Cryptorhynchinae: Tylodina) of Chiapas, Mexico. 1 records from Timea bioxyasterina sp. n., a new species from the Northeastern coast of Brazil (Demospongiae, Hadromerida). 6 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 8 records from Two new and potentially highly threatened Megophrys Horned frogs (Amphibia: Megophryidae) from Indochina’s highest mountains. 1100 records from MijnVISmaat - Exotic fish occurrences in Belgium. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 2 records from Two new species of Sympagella (Porifera: Hexactinellida: Rossellidae) collected from the Clarion-Clipperton Zone, East Pacific. 123941 records from University of Guelph Insect Collection (DEBU). 4 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 16 records from California Soliperla Ricker, 1952 (Plecoptera: Peltoperlidae), Distribution And Taxonomic Characters. 5 records from Integrative description of new giant pill-millipedes from southern Thailand (Diplopoda, Sphaerotheriida, Zephroniidae). 7 records from New species of Culex (Culiciomyia) (Diptera: Culicidae) from Talangaye Forest in Cameroon and descriptions and identification keys for males of the Afrotropical species of the subgenus. 1 records from Revision and redefinition of the crematogastrine ant genus Tetheamyrma BOLTON, 1991, with the description of a new species and the first description of the dealate queen (Hymenoptera: Formicidae). 6 records from Redescription and new records of a poorly known leucosiid crab, Pseudophilyra punctulata Chen & Ng, 2003, and description of a new species of Pseudophilyra from Japan (Crustacea: Decapoda: Brachyura). 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 57 records from Taxonomy of Probolodus Eigenmann, 1911 (Characiformes: Characidae) with description of two new species, and comments about the phylogenetic relationships and biogeography of the genus. 1 records from Epimecia tekes, a new species from south-eastern Kazakhstan (Lepidoptera Noctuidae, Oncocnemidinae). 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 1 records from Overview of bat species reported in Albania with the first country records for eight species. 2 records from One new and four newly recorded species of the genus Macrobrachium (Decapoda: Caridea: Palaemoindae) from Guangdong Province, southern China. 2012 records from Caracterización morfométrica del bagre rayado para la cuenca del Magdalena. 1 records from The mature larva and pupa of Tychius subsulcatus Tournier, 1847 (Coleoptera, Curculionidae), with comments on its biology and phylogenetic relationships. 1 records from The neotropical genus Sporrongia Gumovsky (Hymenoptera: Eulophidae) including two new species and the first biological record. 20 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 46 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 13 records from Five new species of Stenochrus (Schizomida: Hubbardiidae) from Oaxaca, Mexico. 1 records from Two new eriophyoid mite species (Trombidiformes: Eriophyoidea) from the cocoa tree, and a note on Shevtchenkella biseta (Nalepa). 248 records from Taxonomy and distribution of pimpline parasitoids (Hymenoptera, Ichneumonidae, Pimplinae) in Ukraine. 9181 records from NEON Biorepository Mammal Collection (Hair Samples). 1 records from New species and new record of Thraulodes Ulmer, 1920 (Ephemeroptera: Leptophlebiidae: Atalophlebiinae) from Brazil. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 5 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 1 records from Phthiria notiosa sp. nov., a new bombyliid species of the tribe Phthiriini (Diptera Bombyliidae, Phthiriinae) from Kerman province in the south of Iran. 1 records from Happywhale - North Pacific Right Whale in Arctic Ocean. 100 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 3 records from Description of a new species of the genus Pseudepitettix Zheng (Orthoptera Tetrigoidea: Cladonotinae) from China. 3 records from A review of the genera Anasillomos Londt, 1983, Oratostylum Ricardo, 1925, and Remotomyia Londt, 1983, with description of a new genus and two new species (Diptera: Asilidae: Stenopogoninae). 2 records from A new species of Oryttus Spinola, 1836 from the United Arab Emirates and Tunisia with identification key to Palaearctic species (Hymenoptera, Crabronidae). 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 68535 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from A novel member of the Hemidactylus brookii complex (Squamata: Gekkonidae) from the Western Ghats of Maharashtra, India. 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 24 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 2 records from Tomoceridae (Collembola, Entomobryomorpha) from the southern Annamitic cordillera: redescription of Tomocerus ocreatus Denis, 1948 and description of a new species of Tomocerina Yosii, 1955. 16 records from Two new sympatric species of Stenocercus (Squamata: Iguania) from the inter- Andean valley of the Mantaro River, Peru. 8 records from Review of the genus Typhloiulus Latzel, 1884 in the Dinaric region, with a description of four new species and the first description of the male of Typhloiulus insularis Strasser, 1938 (Diplopoda: Julida: Julidae). 4 records from Nomenclatural changes in American Apomecynini including description of new genera and species (Coleoptera: Cerambycidae). 30 records from MVZ Herp Observations (Arctos). 4 records from First record of Psilacrum Becker 1912 (Chloropidae, Diptera) from Brazil, with the description of a new species. 20472 records from Cercle des mycologues de Montréal Fungarium (CMMF). 10 records from A new stiletto fly genus from South America (Diptera: Therevidae: Agapophytinae). 1 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 47 records from Plants Of The Green Line - Woolsthorpe Section. 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 258 records from Systematic census of the private plantations of the firewood of the Benin .. 4 records from Mystus prabini, a new species of catfish (Siluriformes: Bagridae) from Arunachal Pradesh, north-eastern, India. 1 records from A new genus and species of congrid eel from the Philippines (Anguillliformes: Congridae: Bathymyrinae). 80 records from New synonyms, combinations and status in the Chinese species of the family Meloidae Gyllenhal, 1810 (Coleoptera: Tenebrionoidea) with additional faunistic records. 59335 records from USGS South Florida Fish and Invertebrate Assessment Network Crustaceans. 3 records from TWO NEW SPECIES OF ORIPODOIDEA (ACARI: ORIBATIDA) FROM VIETNAM Sergey G. E and Alexander E. A. 2 records from The first record of the family Chloroperlidae (Plecoptera) from the Guangxi Zhuang Autonomous Region of southern China, with description of a new species of Sweltsa Ricker, 1943. 6 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 7383 records from Marie-Victorin Herbarium (MT) - Bryophytes. 26 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 59 records from Neostasina gen. nov., a new genus of huntsman spiders from the Neotropical region (Araneae, Sparassidae, Sparianthinae). 20 records from Bostryx tortoranus (Doering, 1879) species complex (Gastropoda: Stylommatophora: Bulimulidae), a review of taxonomy and distribution of endemic species from Argentina. 202114 records from National Benthic Inventory. 2 records from Happywhale - Arnoux's Beaked Whale in Southern Ocean. 132 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 2 records from Description of four new species of phytoseiid mites belonging to the genus Typhlodromus (Anthoseius) De Leon from West Bengal. 1 records from A new skipper from China: Notocrypta ariannae n. sp. (Lepidoptera, Hesperiidae). 4 records from Supplement to the knowledge of the genus Batraxis Reitter (Coleoptera: Staphylinidae: Pselaphinae) of China. 5 records from A new species of Loricaria (Siluriformes: Loricariidae) from the Turiaçu River basin, Eastern Amazon region, Brazil. 64 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 137028 records from Arizona State University Hasbrouck Insect Collection. 4 records from A new genus of katydid from the Amazon Rainforest (Orthoptera: Tettigoniidae; Phaneropterinae; Steirodontini): Ninth contribution to the suprageneric organization of the Neotropical phaneropterines. 35 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 1 records from A new diurnal gecko in the genus Gonatodes (Squamata: Sphaerodactylidae) from Margarita Island, Venezuela. 13 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 2 records from Happywhale - Adelie Penguin in Southern Ocean. 3 records from Happywhale - Risso's Dolphin in South Pacific Ocean. 179 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 4 records from A new species of Synotaxus and the first chromosomal study on Synotaxidae, presenting a rare XY sex chromosome system in spiders (Araneae, Araneoidea). 1 records from A new species of the genus Gracixalus (Amphibia: Anura: Rhacophoridae) from Mount Jinggang, southeastern China. 11 records from Phylogenomic re-evaluation of Triaenonychoidea (Opiliones: Laniatores), and systematics of Triaenonychidae, including new families, genera and species. 14 records from Taxonomy of the Neolycaena (Rhymnaria) davidi (Oberthür, 1881) species group with the description of two new taxa from Russia and China (Lepidoptera, Lycaenidae). 8 records from The catshark genus Scyliorhinus (Chondrichthyes: Carcharhiniformes: Scyliorhinidae): taxonomy, morphology and distribution. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 1 records from Calvariopsis gen. nov., a new genus of Neotropical Scirtidae (Coleoptera: Scirtoidea). 954 records from NW Pacific Deep-sea Benthos Biodiversity (Beneficial Project). 47432 records from Phanerogamic Botanical Collections (S). 40 records from Review of the genera Pristocera Klug and Pristepyris Kieffer (Hymenoptera Bethylidae, Pristocerinae) of Russia and adjacent territories. 16 records from A study on the genus Stenus Latreille from Zhuji City of Zhejiang, East China (Coleoptera, Staphylinidae). 4 records from A review of the Callogobius (Teleostei: Gobiidae) from the Red Sea with the description of a new species. 2 records from Ukamenia Oku, 1981 (Lepidoptera: Tortricidae: Olethreutinae), new record for Thailand with descriptions of a new species. 1 records from A new species of genus Oxytauchira from India (Orthoptera: Acrididae). 21 records from Descriptions of a new species and previously unknown males of Nesticus (Araneae: Nesticidae) from caves in Eastern North America, with comments on species rarity. 2 records from Potamonautes nheenae, a new species of freshwater crab from Gabon, Central Africa, with a description of the first known male of Erimetopus brazzae (A. Milne-Edwards, 1886) from the Democratic Republic of the Congo, Central Africa (Brachyura: Potamoidea: Potamonautidae). 53 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 40 records from A New Species Of Isoperla Banks (Plecoptera: Perlodidae) From The Southern Appalachians, With Notes On The I. Montana Group. 2 records from A strikingly coloured new giant millipede from Vietnam has copycat in Borneo (Diplopoda, Spirostreptida, Harpagophoridae). 6 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 2 records from Descripción de una nueva especie del grupo Drosophila tripunctata (Diptera: Drosophilidae) en Cruz Loma, Pichincha, Ecuador. 6 records from On two sibling Lathys species (Araneae, Dictynidae) from northern Europe. 2 records from A new species of Bolitoglossa (Caudata: Plethodontidae) of the Bolitoglossa franklini group from an isolated cloud forest in northern Guatemala. 23 records from Two new species and new records of terrestrial isopods (Crustacea, Isopoda, Oniscidea) from Brazilian caves. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 21 records from Family groups of Diopsoidea and Nerioidea (Diptera: Schizophora) - Definition, history and relationships. 5 records from Three new species of Ischioscia Verhoeff, 1928 (Isopoda, Oniscidea, Philosciidae) from Serranía de Perijá, Andean Cordillera, Colombian Caribbean. 55 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 1 records from Aloe trinervis sp. nov.: A new succulent species from Indian Desert (Asphodelaceae). 1 records from A new species of tooth-carp, Aphanius mesopotamicus, from Iran and Iraq (Actinopterygii, Cyprinodontidae). 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 2 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 13 records from Deep sea Syllidae (Annelida, Phyllodocida) from Southwestern Atlantic. 17755 records from K-State Museum of Entomological and Prairie Arthropod Research. 9 records from Description of a new genus and species of Chrysopetalidae (Annelida: Polychaeta) from the NE Atlantic, with some further records of related species. 4 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 92 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 3 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 186 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 4 records from A new species of Celidodacus Hendel, with notes on C. coloniarum (Speiser) and C. obnubilus (Karsch). 2 records from A new genus and two new species of arctiine tiger moth (Noctuidae, Arctiinae, Arctiini) from Costa Rica. 171 records from Studies on the Australian Muscidae (Diptera). VIII. The genus Lispe Latreille, 1797. 5229 records from European Moth Nights. 4 records from Two more new Hemiphyllodactylus Bleeker, 1860 (Squamata: Gekkonidae) from Tamil Nadu, India. 11 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 2 records from Macedomeris, a new monotypic doderiinine genus (Diplopoda, Glomerida) from a cave in North Macedonia, Balkan Peninsula. 12 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae) from the Orinoco River basin. 14 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 3 records from Taxonomic review of Athliini (Coleoptera: Scarabaeidae: Melolonthinae), a new tribe of scarab beetles endemic to South America. 7 records from The genus Stactobiella Martynov (Trichoptera, Hydroptilidae) in Japan. 2 records from Integrative descriptions of two new species of Dugesia from Hainan Island, China (Platyhelminthes, Tricladida, Dugesiidae). 5 records from Two New Species Of Stoneflies In The Leuctra Ferruginea Group (Plecoptera: Leuctridae), With Notes On The Leuctra Species Known For Mississippi And Alabama, U. S. A.. 4 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 4 records from A new species of Geodromicus Redtenbacher, 1857 from Sichuan (Coleoptera Staphylinidae: Omaliinae: Anthophagini). 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 2 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 4 records from Two new species of the genus Deltomerodes Deuve, 1992 (Coleoptera, Carabidae, Patrobini) from Xizang, China. 136 records from Three new species, Elathous zagrosensis sp. n., Zorochros dilatatus sp. n., and Dicronychus iranicus sp. n., and noteworthy records of click beetles from western Iran (Coleoptera: Elateridae). 1 records from Coarazuphium lundi (Carabidae: Zuphiini), a new Brazilian troglobitic beetle with the designation of a neotype for C. pains Álvares & Ferreira, 2002. 11 records from A review of the Asian orb weaving spider genus Pronoides (Araneae: Araneidae). 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 2 records from Two new species of the Rhyacophila nigrocephala species group from China (Insecta, Trichoptera, Rhyacophilidae). 2 records from A new species of the genus Oligodon Fitzinger, 1826 (Squamata: Colubridae) from Cu Lao Cham Islands, central Vietnam. 5 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 32 records from Barsura Volynkin, Dubatolov & Kishida, gen. nov., with descriptions of three new species (Lepidoptera, Erebidae, Arctiinae). 4 records from A review of the genus Trachystolodes Breuning, 1943 (Coleoptera: Cerambycidae Lamiinae: Lamiini). 2533 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 2 records from A new groundwater-dwelling species of Euryrhynchina from Cameroon (Malacostraca, Decapoda, Euryrhynchidae). 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 4 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 11 records from A survey of East Palaearctic Gnaphosidae (Araneae). 5. On Synaphosus from Central Asia. 80 records from DNA Barcoding and Integrative Taxonomy of the Heterolepisma sclerophylla species complex (Zygentoma: Lepismatidae: Heterolepismatinae) and the Description of Two New Species. 4 records from A new species of Tetragonopterus Cuvier, 1816 (Characiformes: Characidae: Tetragonopterinae) from the rio Jari, Amapá, northern Brazil. 1 records from A new species of Acanthosaura Gray 1831 (Reptilia: Agamidae) from central Vietnam. 1 records from A new species in the Trachusa ovata species group (Hymenoptera: Apoidea) from Peninsular Malaysia with an overview of the old-world species within the genus Trachusa. 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 4 records from Cliona acephala (Porifera: Demospongiae: Clionaida), a new encrusting excavating reef sponge from the Colombian Caribbean belonging to the Cliona viridis species complex. 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 12 records from Description of three new species of biting midge of the genus Atrichopogon Kieffer (Diptera: Ceratopogonidae) from Brazilian Amazon. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 5 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 9 records from New species and stages description of Traverella Edmunds, 1948 (Ephemeroptera Leptophlebiidae) from Northeast Brazil. 6 records from A new species of Anurophorus (Collembola: Isotomidae) from South Korea, with notes on its molecular data. 1 records from Mycetocharina (Alleculopsis) bahukalatensis sp. nov. (Coleoptera: Tenebrionidae: Alleculinae) from Iran. 3 records from Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Martínez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 2 records from A new species of Pasiphaea Savigny, 1816 (Crustacea, Decapoda, Pasiphaeidae) from the southwestern Atlantic. 1459 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2009. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 10075 records from Nematoda of Costa Rica (INBio). 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 1 records from DNA barcodes and morphology confirm a new species of Rheocricotopus (Psilocricotopus) orientalis group (Diptera: Chironomidae). 6 records from Revision of the family Acidopsidae Števčić, 2005, and the systematic position of Typhlocarcinodes Alcock, 1900, Caecopilumnus Borradaile, 1902, and Raoulia Ng, 1987, with descriptions of two new genera and five new species (Crustacea: Brachyura: Goneplacoidea). 18 records from Two new species of Curculionichthys (Siluriformes: Loricariidae) from the rio Amazonas basin, Brazil. 4 records from Two more new species of the Cyrtodactylus peguensis group (Squamata: Gekkonidae) from the fringes of the Ayeyarwady Basin, Myanmar. 2 records from Happywhale - Southern Bottlenose Whale in Southern Ocean. 7359 records from Crustaceos del Museo de Ciencias naturales de la Universidad Simón Bolívar. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 2 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 78 records from New species and records of Caulleriella (Annelida, Cirratulidae) from shelf and slope depths of the Western North Atlantic Ocean. 1 records from A new species of Tapiena (Orthoptera: Tettigonioidea: Phaneropterinae) from Brunei Darussalam (Borneo, Southeast Asia). 12 records from Three new ghost moths of the genus Oxycanus Walker, 1856 from Australia (Lepidoptera: Hepialidae). 11 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 100 records from Brock University Herbarium (BU). 12 records from Descriptions of eight new species of the genus Parancistrocerus Bequaert (Hymenoptera: Vespidae: Eumeninae), with a key to the Oriental species. 23 records from Five species of the genus Epicephala Meyrick, 1880 (Lepidoptera: Gracillariidae) from China. 9 records from Three new species of earthworms (Oligochaeta: Megascolecidae) from Yunnan Province, China. 998 records from Invasive Alien plant species of Malawi. 1 records from Haruchlora maesi, a new emerald moth genus and species from Mesoamerica (Lepidoptera, Geometridae, Geometrinae). 38 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 42979 records from The census of national forest of Benin .. 13 records from Seven new species of Loneura Navás (Insecta: Psocodea: ‘ Psocoptera’: Ptiloneuridae) from Valle del Cauca, Colombia. 1 records from First record of a living ditaxiporine catenicellid in the Atlantic, with a description of Vasignyella ovicellata n. sp. (Bryozoa). 57973 records from Mammals Specimens. 1 records from Two new species of the genus Metaxonchium Coomans & Nair, 1975 (Nematoda, Dorylaimida, Belondiridae) from Vietnam. 5 records from Three new species of deep-sea Gromia (Protista, Rhizaria) from the bathyal and abyssal Weddell Sea, Antarctica. 4 records from Two new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from Guizhou and Guangxi, China. 1 records from First record of spongillaflies (Neuroptera: Sisyridae) from Colombia. 3 records from Review of the Swedish Enicospilus (Hymenoptera; Ichneumonidae; Ophioninae) with description of three new species and an illustrated key to species. 27 records from Review of the species of the genus Serrapinnus Malabarba, 1998 (Teleostei: Characidae: Cheirodontinae) from the rio Tocantins-Araguaia basin, with description of three new species. 1 records from A new species and new record of Polycystididae (Rhabdocoela: Kalyptorhynchia) from China. 87 records from Dichomeris Hübner, 1818 (Lepidoptera, Gelechiidae, Dichomeridinae) from Cambodia, including associated Chinese species. 27344 records from Condon Fossil Collection - Oregon Museum of Natural and Cultural History. 12 records from Oxynoemacheilus nasreddini, a new nemacheilid loach from Central Anatolia (Teleostei: Nemacheilidae). 3 records from A new species-group with new species of the genus Lasioseius (Acari: Mesostigmata: Blattisociidae) associated with Neotropical hispine beetles in furled leaves ofHeliconia. 4 records from New Species And Records Of Anacroneuria (Plecoptera: Perlidae) From Ecuador And Paraguay. 17 records from A new species and new country records for the genus Leptobium Casey in the Palaearctic Region (Coleoptera: Staphylinidae: Paederinae). 1 records from Isoperla vjosae sp. n., a new species of the Isoperla tripartita group from Albania (Plecoptera: Perlodidae). 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 1 records from Three New Species of Dendrogaster (Crustacea: Ascothoracida) Infecting Goniasterid Sea-Stars (Echinodermata: Asteroidea) from Japan. 162 records from New data on spiders (Aranei) from the Maritime Province, Russian Far East. 5 records from Review of the species of Stenothemus from Southeast China (Coleoptera, Cantharidae). 3148 records from Intermountain Herbarium (fungi, not lichens), Utah State University. 2 records from Trachelus stipa (Hymenoptera: Cephidae), a new stem sawfly from Central Anatolia associated with feather grass (Stipa holosericea, Poaceae). 19 records from Revision of the Barsine cardinalis - anomala ' species-complex' (Lepidoptera, Erebidae, Arctiinae). 26 records from A checklist of the Iranian Mordellidae (Coleoptera: Tenebrionoidea). 1 records from Dressed in black. A New Ansonia Stoliczka, 1870 (Lissamphibia: Anura: Bufonidae) from Gunung Murud, Sarawak, East Malaysia (Borneo). 95801 records from CAS Entomology (ENT). 2 records from Notes on Anomala felicia A ,, 1910 and its relatives from Borneo with descriptions of six new species (Coleoptera: Scarabaeidae: Rutelinae). 18 records from Swedish Malaise Trap Project (SMTP) - Diacritinae. 6048 records from Naturalis Biodiversity Center (NL) - Pisces. 27 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 28 records from Tenuiphantes zelatus (Zorsch), T. zibus (Zorsch), and Centromerus mariannae sp. nov. (Araneae: Linyphiidae) in the Pacific Northwest. 2968 records from John Clayton's Fijian Moth Collection. 12 records from Species delimitation in the Gehyra nana (Squamata: Gekkonidae) complex: cryptic and divergent morphological evolution in the Australian Monsoonal Tropics, with the description of four new species. 3 records from The genus Phlesirtes Bolivar, 1922 (Orthoptera: Tettigoniidae: Conocephalinae, Conocephalini; Karniellina), a review of the genus with data on its bioacoustics and the description of new species. 5 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 20 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 53 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 11 records from The Endemic Sulawesi Fish Genus Lagusia (Teleostei: Terapontidae). 9 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 6 records from A taxonomic revision of the genus Sirthenea (Hemiptera: Heteroptera: Reduviidae) of the Old World. 17 records from The genus Stenoterommata Holmberg, 1881 (Araneae, Pycnothelidae) in the Cerrado and Atlantic Forest from Southeastern and Central Brazil: description of four new species. 16 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 4 records from Carnivorous sponges (Porifera, Cladorhizidae) from the deep South Pacific (New Caledonia) with the description of three new species of the genus Abyssocladia and remarks on genus Cercicladia. 6 records from Review of Chinese littoral Thalassaphorura (Collembola: Onychiuridae), with the description of two new species. 2 records from Rafflesia verrucosa (Rafflesiaceae), a new species of small-flowered Rafflesia from eastern Mindanao, Philippines. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 897 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 24 records from Western Hemisphere Lasiochilinae (Hemiptera: Heteroptera: Anthocoridae) with comments on some extralimital species and some considerations on suprageneric relationships. 2 records from The deep-water Calappidae, Matutidae and Leucosiidae of the Solomon Islands, with a description of a new species of Euclosia Galil, 2003 (Crustacea, Decapoda, Brachyura). 118 records from Taxonomy and host-plant relationships of the psyllid genus Mitrapsylla (Hemiptera: Psylloidea: Psyllidae) in Brazil. 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 3 records from Kenai National Wildlife Refuge, Alaska (KNWR) Mammal observations (Arctos). 7 records from Paraorosius, a new genus of leafhopper (Hemiptera: Cicadellidae: Deltocephalinae: Opsiini), with description of a new species from the Middle East. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 4 records from DNA barcoding of the genus Dichopygina, with a new species from China (Diptera: Sciaridae). 3277 records from USAC Mammals Collection. 21 records from Perlesta armitagei n. sp. (Plecoptera: Perlidae): More cryptic diversity in darkly pigmented Perlesta from the eastern Nearctic. 3 records from Happywhale - Dusky Dolphin in South Pacific Ocean. 3 records from A new species of the genus Colilodion Besuchet, 1991 (Coleoptera: Staphylinidae: Pselaphinae) from Mindanao, the Philippines. 46 records from Unexpected diversity of the genus Collarina Jullien, 1886 (Bryozoa, Cheilostomatida) in the NE Atlantic-Mediterranean region: new species and reappraisal of C. balzaci (Audouin, 1826) and C. fayalensis Harmelin, 1978. 1 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 16 records from The spider family Oecobiidae (Arachnida: Araneae) in Iran, Afghanistan and Turkmenistan. 32 records from The jumping plant-lice of the Neotropical genus Tainarys (Hemiptera: Psylloidea) associated with Anacardiaceae. 4 records from A new species of Ergasilus von Nordmann, 1832 (Copepoda: Cyclopoida) from the gills of a dasyatid ray, Himantura oxyrhyncha (Sauvage, 1878) from West Kalimantan, Indonesia. 23 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 2 records from A new species of Glyptothorax (Teleostei: Sisoridae) from the Brahmaputra River basin, Arunachal Pradesh, India. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 7 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 4563 records from Sizing Ocean Giants. 5 records from Morphological description and DNA barcoding of Hydrobaenus laticaudus Saether 1976 (Diptera: Chironomidae: Orthocladiinae) from Amur River basin (Russian Far East). 1265 records from Synopsis of Schizanthus: list of specimens examined. 1 records from Taxonomy of some Galeommatoidea (Mollusca, Bivalvia) associated with deep-sea echinoids: A reassessment of the bivalve genera Axinodon Verrill & Bush, 1898 and Kelliola Dall, 1899 with descriptions of new genera Syssitomya gen. nov. and Ptilomyax gen. nov.. 21 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 6 records from Four new species of Scydmaeninae and Pselaphinae (Coleoptera: Staphylinidae) from Yunnan, China. 1 records from A new species of frog in the Litoria ewingii species group (Anura: Pelodryadidae) from south-eastern Australia. 1 records from Adamastoraltica humicola, new genus and new species: the first example of possible moss-inhabiting flea beetle genus from sub-Saharan Africa (Coleoptera Chrysomelidae, Galerucinae). 3406 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 10 records from Laophontodes typicus T. Scott (Copepoda, Harpacticoida, Laophontodinae) - discovering a species complex by morphology. 1 records from Two new species of the genus Gibbotettix Zheng, 1992 (Orthoptera: Tetrigidae, Cladonotinae) from China. 76 records from Occurrence data of Eremohaplomydas, Haplomydas, and Lachnocorynus (Diptera: Asiloidea: Mydidae). 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 72 records from Swedish Malaise Trap Project (SMTP) - Xoridinae. 25 records from Cladistics and revision of Alitocoris with considerations on the phylogeny of the Herrichella clade (Hemiptera, Pentatomidae, Discocephalinae, Ochlerini). 22 records from The fishery ground near Alexandria. XVI. Cumacea, stomatopoda, leptostraca by Adolf Steuer (1938).Notes and Memoirs No 26.. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 2 records from Two new butterfly species (Lepidoptera: Rhopalocera) from Mount Cameroon, Gulf of Guinea Highlands, Cameroon. 1 records from A new species of the ghost shrimp genus Neocallichirus Sakai, 1988 from Iran, and new record of N. manningi Kazmi & Kazmi, 1992 (Decapoda: Axiidea: Callianassidae). 2 records from Description of the second species of Synhalcurias Carlgren, 1914, Synhalcurias kahakui sp. nov. (Actiniaria: Actinernidae) with redescription of S. elegans (Wassilieff, 1908). 43418 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 3 records from Two new species of freshwater crabs from the highlands of northern Uganda, East Africa and a redescription of Potamonautes amalerensis (Rathbun, 1935) stat. rev. from Mount Kadam (Brachyura: Potamoidea: Potamonautidae). 3 records from Taxonomy and natural history of the myrmecophilous genus Clinterocera Motschulsky, 1858 (Coleoptera: Scarabaeidae: Cetoniinae) from China and adjacent regions: revision of the C. jucunda species group. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 4 records from A new species of the remarkable brittle star genus Astrophiura (Echinodermata: Ophiuroidea) from the western Atlantic Ocean. 6445 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 1 records from Description of a new Gibbaranea (Araneae: Araneidae) from the Western Mediterranean. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 1 records from A new species of Parafimbrios from northern Vietnam (Squamata: Xenodermatidae). 1 records from A new deepwater gurnard of the genus Pterygotrigla (Scorpaeniformes: Triglidae) from the southwestern Indian Ocean. 45 records from New species, a new combination, and a new country record in American Clytini (Coleoptera: Cerambycidae: Cerambycinae). 16 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 5 records from Two new species of Eumeninae from Iran (Hymenoptera: Vespidae). 24 records from Mantidflies (Neuroptera, Mantispidae) from Tocantins state (Brazil): distribution and identification key. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 4 records from A new species of Stasimopus from the Eastern Cape Province of South Africa (Araneae, Mygalomorphae, Ctenizidae), with notes on its natural history. 1 records from Chenopodium vulvaria. 5 records from Two New Shallow-water Species of Agathotanais (Crustacea: Tanaidacea) from Japan. 6 records from The genus Ctenomelynthus (Hemiptera: Heteroptera: Coreidae: Acanthocephalini), with the description of three new species and key to the known species. 2 records from Two new species of Tanytarsus van der Wulp (Diptera: Chironomidae) from Costa Rica. 42 records from Contribution to the knowledge of the earthworm fauna of Turkey with description of three new species (Clitellata: Megadrili). 2 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 3689 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 7 records from Taxonomic study of the genus Hypatopa Walsingham, 1907 (Lepidoptera: Blastobasidae) in China, with descriptions of five new species. 176 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 4 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 3 records from Contribution to the knowledge of Dialeurodes (Gigaleurodes) Quaintance & Baker (Hemiptera: Aleyrodidae), with description of a new species from China. 190 records from NEON Biorepository Benthic Macroinvertebrate Collection (DNA Extracts). 8 records from Taxonomic revision of Plyomydas Wilcox & Papavero, 1971 with the description of two new species and its transfer to Mydinae (Insecta: Diptera: Mydidae). 3 records from Vietelmis jablonskii, a new species of riffle beetle from Laos and Thailand and new faunistic records on Vietelmis Delève, 1968 from Malaysia (Coleoptera: Elmidae). 4 records from A new black fly species of Simulium (Simulium) (Diptera: Simuliidae) from Taiwan. 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 3 records from A new Antillobisium species (Arachnida: Pseudoscorpiones: Bochicidae) from Cuba, with biogeographical and ecological remarks on the genus. 2 records from A new species of the genus Hebius (Squamata: Colubridae: Natricinae) from Hunan Province, China. 9 records from Revision of Pseudexogone Augener, 1922 (Annelida, Polychaeta, Syllidae), and its transfer to Pilargidae. 7 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 3 records from Systematics of Helioandesia tarregai gen. et sp. nov. (Lepidoptera: Yponomeutoidea: Heliodinidae) from the Andes of Northern Chile. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 63 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 2 records from Family Rhinolophidae. Horseshoe Bats in Checklist of African Mammals. 2 records from New data on the taxonomy, ecology, and conservation of the rediscovered Louisea edeaensis (Bott, 1969) (Brachyura: Potamoidea: Potamonautidae), an endangered freshwater crab from Cameroon. 2421 records from Census of plant species in Toffo forest reserve. 1 records from A new long-legged terrestrial freshwater crab, Calcipotamon puglabrum gen. nov et sp. nov. (Crustacea: Decapoda: Potamidae), from Hainan Island, China. 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 19 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 39190 records from Freshwater fishes of Poland. 1 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 15 records from Leafhopper subfamily Ledrinae of the Indian subcontinent: 1. Description of Yelahanka gen. nov. (Hemiptera: Cicadellidae) with seven new species and new combinations. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 2 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 17 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 4 records from Further information on Lolibaia Gorbunov & Gurko, 2017 (Lepidoptera: Sesiidae: Synanthedonini) with description of three new species from tropical Africa. 13 records from Pyura (Tunicata: Ascidiacea: Pyuridae) on the coasts of Panama. 1081 records from Riparian Vegetation Survey of Lower Okavango Delta by Ringrose and Matheson 1999. 1 records from A new species of the genus Parahormius Nixon (Hymenoptera: Braconidae: Hormiinae) parasitic on host pupae of Lyonetiidae (Lepidoptera) from India. 906823 records from Museums Victoria provider for OZCAM. 41 records from Proper cleaning of keratin beetles reveals a cryptic species: Phoberus fumarius (Haaf, 1953) from southern Africa is reinstated as valid (Coleoptera: Trogidae). 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 5 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 1 records from A new amphibious troglobitic styloniscid from Brazil (Isopoda, Oniscidea, Synocheta). 8 records from Epimeria cleo sp. nov., a new crested amphipod from the Ross Sea, Antarctica, with notes on its phylogenetic affinities (Crustacea, Amphipoda, Eusiroidea, Epimeriidae). 1 records from Complementary Description Of Anacroneuria Izapa (Plecoptera: Perlidae) From Mexico. 5 records from Two new species of Ocyochterus (Heteroptera: Ochteridae) from Ecuador and Panama. 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 2 records from Colaphellus palaestinus Achard, a new leaf-beetle for Europe (Coleoptera, Chrysomelidae, Chrysomelinae). 10 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 97 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 2 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 4 records from Redescription of Alopecosa albostriata (Araneae: Lycosidae) based on specimens from Siberia. 2 records from The genus Eodendrus Belokobylskij (Hymenoptera, Braconidae, Doryctinae) from China, with description of a new species. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 2 records from Genetic and morphological evidence for a new cryptic species of Ectinogonia (Coleoptera: Buprestidae) from central Chile. 10 records from The West and Central African species of Vepris Comm. ex A. Juss. (Rutaceae) with simple or unifoliolate leaves, including two new combinations. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from Dombeya sevathianii (Malvaceae): A new critically endangered species endemic to Mauritius (Indian Ocean). 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 38 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 155 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 15 records from Collections de coquilles continentales du Muséum d'histoire naturelle de Grenoble. 1 records from Pyrrosia sarthalensis, a new species of Polypodiaceae from Kathua District, Jammu and Kashmir, Western Himalaya, India. 1 records from Planothidium galaicum sp. nov. (Bacillariophyta, Achnanthidiaceae), a new diatom species from Galician coast, Spain. 12 records from Four new species of the genus Rhodesiella from Xizang Autonomous Region, China (Diptera: Chloropidae). 4 records from Troglocaris (Xiphocaridinella) kumistavi sp. nov., a new species of stygobiotic atyid shrimp (Crustacea: Decapoda: Atyidae) from Kumistavi Cave, Imereti, Western Georgia, Caucasus. 2 records from Revision of Pleuroprion zur Strassen, 1903 (Holidoteidae) and re-evaluation of Spectrarcturus Schultz, 1981 (Arcturidae) (Crustacea, Isopoda, Valvifera). 4 records from Two new marine cyclopinids (Crustacea: Copepoda: Cyclopoida) from interstitial habitats in Korea. 33814 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 3 records from Cylindroniscus platoi (Isopoda: Oniscidea: Styloniscidae), a new cave-dwelling species from Lagoa Santa Karst, Southeastern Brazil. 3 records from Happywhale - Short-finned Pilot Whale in South Atlantic Ocean. 6 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 6 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 1 records from Genetic and morphological evidence for cryptic species in Macrobrachium australe and resurrection of M. ustulatum (Crustacea, Palaemonidae). 1616 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 1 records from A large hornet mimic clearwing moth of the genus Lamellisphecia Kallies & Arita 2004 (Lepidoptera, Sesiidae) from Nanling, Guangdong, southern China. 1 records from A new species of Merothrips from the Dampa Tiger Reserve, Mizoram, India (Thysanoptera, Terebrantia). 1 records from Beyond shells: first detailed morphological description of the mangrove-associated gastropod Haminoea cf. fusca (A. Adams, 1850) (Cephalaspidea, Haminoeidae), with a COI phylogenetic analysis. 1597 records from Meetnetten.be - Egg counts for butterflies in Flanders, Belgium. 12 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 1 records from An Update On The Stonefly Fauna (Insecta, Plecoptera) Of Maryland, Including New And Emended State Records And An Updated State Checklist. 1 records from A new species of alpheid shrimp tentatively assigned to Salmoneus Holthuis, 1955 (Decapoda: Caridea) from the Ryukyu Islands, Japan. 13 records from Review of Poecilimon species with inflated pronotum: description of four new taxa within an acoustically diverse group. 83 records from Mexican species of the genus Orthocentrus (Hymenoptera, Ichneumonidae: Orthocentrinae). 36 records from University of Sindh Jamshoro Herbarium. 2 records from A New Genus of the Spider Family Caponiidae (Araneae, Haplogynae) from the West Indies. 8 records from Disentangling vines: a study of morphological crypsis and genetic divergence in vine snakes (Squamata: Colubridae: Ahaetulla) with the description of five new species from Peninsular India. 8 records from Happywhale - King Penguin in South Atlantic Ocean. 29 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 5 records from The Apseudomorpha (Crustacea: Tanaidacea) of the Gulf of Cadiz and Horseshoe Continental Rise (NE Atlantic): A taxonomic review with new records, species, and ecological data. 1 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 62 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 3 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 125 records from Mica - Muskrat, Raccoon and Coypu occurrences collected by ITAW in Germany. 2 records from Revision of Taurocerus (Heteroptera, Pentatomidae, Pentatomini). 3 records from Onthophagus fragosus n. sp. a second endemic species of Onthophagus Latreille from Cuba (Coleoptera: Scarabaeidae, Scarabaeinae). 2 records from A new genus of Pharaxonothinae from Australia (Coleoptera: Erotylidae). 13 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 4 records from Two new species of Atlantoscia Ferrara & Taiti, 1981 (Isopoda: Oniscidea: Philosciidae) from southern Brazil described in the light of integrative taxonomy. 5 records from Two new species of Paratanytarsus Thienemann & Bause (Diptera: Chironomidae) from Oriental China. 2 records from Two new species of the genus Atractoscion, and resurrection of the species Atractoscion atelodus (Günther 1867) (Perciformes: Sciaenidae). 3 records from Flightless Catapionus (Coleoptera: Curculionidae: Entiminae) in Southwest China survive the Holocene trapped on mountaintops: new species, unknown phylogeny and clogging taxonomy. 7 records from New endemic species of freshwater crayfish Parastacus Huxley, 1879 (Crustacea: Decapoda: Parastacidae) from the Atlantic forest in southern Brazil. 2 records from New Descriptions Of North American Taenionema Larvae (Plecoptera: Taeniopterygidae). 6 records from A new species of turtle-headed sea Snake (Emydocephalus: Elapidae) endemic to Western Australia. 6 records from Systematics of New Guinea treefrogs (Litoria: Pelodryadidae) with erectile rostral spikes: an extended description of Litoria pronimia and a new species from the Foja Mountains. 3 records from A name for the nurse-frog (Allobates, Aromobatidae) of Floresta Nacional de Carajás, Eastern Brazilian Amazonia. 111 records from Revision of the Australian species of Anatomidae (Mollusca: Gastropoda: Vetigastropoda). 2 records from Description of female of Titidius urucu Esmerio & Lise, 1996 (Araneae: Thomisidae). 35 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 12 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 1 records from Systematic revision of Central American Calligrapha Chevrolat of the subgenus Erythrographa subgen. nov. (Coleoptera: Chrysomelidae, Chrysomelinae). 3 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 8 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 1 records from New species of Raphidascaris (Sprentascaris) (Nematoda: Anisakidae) in Rineloricaria steinbachi (Actinopterygii: Loricariidae) from Northwest Argentina. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 26 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 4 records from A new species of small and highly abbreviated caecilian (Gymnophiona: Indotyphlidae) from the Seychelles island of Praslin, and a recharacterization of Hypogeophis brevis Boulenger, 1911. 1334 records from Happywhale - Gray Whale in North Pacific Ocean. 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 15 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 17 records from Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region. 2 records from A new species of Plurellidae (Ascidiacea: Phlebobranchia) from Papua New Guinea. 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 1 records from Systematic redescription of Solen (Ensisolen) tehuelchus and Ensis macha (Bivalvia: Solenoidea) from Argentina, southwestern Atlantic Ocean. 5 records from The Stenus cirrus group (Coleoptera, Staphylinidae) in Fujian, East China. 4 records from Confirmation of Gonioctena rufa (Kraatz, 1879) (Coleoptera: Chrysomelidae) in northeastern Asia, previously misinterpreted as a subspecies of G. viminalis (Linnaeus, 1758), and a new synonym in the genus. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 199 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 1 records from A new species of nurse-frog (Aromobatidae, Allobates) from the Madeira River basin with a small geographic range. 11 records from Three new species of Thaloe Brescovit (Araneae: Anyphaenidae: Anyphaeninae), with descriptions of the first known females of the genus. 318 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 9 records from New species and findings of Pagastia Oliver (Diptera: Chironomidae: Diamesinae) from Central Asia, with DNA barcoding of known species of the genus. 4 records from Gammaropsis elvirae sp. nov., a widely distributed amphipod (Amphipoda: Photidae) in the Yucatan Shelf, with ecological comments and a key for the genus in tropical America. 7 records from Four new cyclophoroid species from Thailand and Laos (Gastropoda: Caenogastropoda: Alycaeidae, Diplommatinidae, Pupinidae). 2 records from Review of lady beetles in the Cycloneda germainii species complex (Coleoptera; Coccinellidae: Coccinellinae: Coccinellini) with descriptions of new and unusual species from Chile and surrounding countries. 43 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 10907 records from Census of species recorded during phytosociological surveys in Benin. 4 records from Discovery of leaf-mining Tischeriidae (Lepidoptera) in Colombia and their distribution in the Neotropics. 6 records from Oxynoemacheilus kentritensis, a new species from the upper Tigris drainage in Turkey with remarks on O. frenatus (Teleostei: Nemacheilidae). 10 records from Cladistic analysis and description of a new species of the Brazilian genus Atlantodesmus Hoffman, 2000 (Diplopoda: Polydesmida: Chelodesmidae). 30 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) IX. The maculosa species-group, with descriptions of eighteen new species. 2 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 1 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 5 records from Three new species of the spider genus Belisana Thorell, 1898 (Araneae: Pholcidae) from Xishuangbanna, Yunnan, China. 4 records from Descriptions of three new species of Odonata from Brazil. 225 records from Data from ILAM surveys conducted by ARCOS in Mukura landscape for year 2016. 781 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 32 records from Three new species of Mesovelia Mulsant & Rey (Hemiptera: Heteroptera: Mesoveliidae) from India. 3 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 30 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 56268 records from Florida Keys Reef Visual Census 2007. 52 records from The caddisfly genus Triaenodes in the Neotropics (Trichoptera: Leptoceridae). 2 records from Thalictrum nanhuaense (Ranunculaceae), a new species from central Yunnan, China. 2 records from A taxonomic synopsis of Chrysomydas Wilcox, Papavero & Pimentel (Diptera: Mydidae: Mydinae), with first bionomic records for the genus and description of a new species from Brazil. 4 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 7 records from Macropsini (Hemiptera: Cicadellidae) of Thailand, with description of two new species and three new country records. 9 records from New discoveries for the subfamily Phtisicinae Vassilenko, 1968 (Crustacea: Senticaudata) from the Brazilian coast. 4 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 2 records from A new species of the porcelain crab genus Petrolisthes from the Pacific coast of Panama, with taxonomic notes on closely related species (Decapoda: Anomura Porcellanidae). 13 records from First record of Africactenus Hyatt, 1954 and redescriptions of two poorly known species of Ctenus Walckenaer, 1805 (Araneae, Ctenidae, Cteninae) from India. 1 records from Review of Lecithoceridae (Lepidoptera: Gelechioidea) in the Oceanian Region, with description of a new species and a checklist of the family. 16 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 1 records from First Record of Holothuria (Cystipus) dura (Echinodermata: Holothuroidea) from Japan, with Notes on Locomotion. 356 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 1 records from Three new peculiar species of the genus Miltochrista Hübner, [1819] from China (Lepidoptera, Erebidae, Arctiinae). 2 records from Two new species of Dactylonotus Parent, 1934 (Diptera: Dolichopodidae) from South Africa and a key to Afrotropical species. 3 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 434 records from A revision of the minor species group in the millipede genus Nannaria Chamberlin, 1918 (Diplopoda, Polydesmida, Xystodesmidae). 5 records from One new Pseudopoda species group (Araneae: Sparassidae) from Yunnan Province, China, with description of three new species. 9 records from Revision of Khoikhoiinae (Hymenoptera, Braconidae). 1 records from A new genus and species of a terrestrial cavernicolan planarian from Barro Colorado Island, Panama (Platyhelminthes, Tricladida, Cavernicola). 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 9 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 6 records from Two new species of the genus Trilacuna from Chongqing Municipality, China (Araneae, Oonopidae). 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 88396 records from Herbarium Willing at Herbarium Berolinense, Berlin (B). 5 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 52 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 7 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 1 records from New species, redescriptions and phylogenetic revision of tribe Dacini (Diptera: Tephritidae: Dacinae) from India based on morphological characters. 11686 records from NCSM Mammalogy Collection. 15 records from Review of the genus Trichactia Stein (Diptera: Tachinidae) in the Palaearctic Region, with the description of a new species from Iran and the East Mediterranean. 24 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 2 records from Notes on Malagasy Discheramocephalus Johnson (Coleoptera: Ptiliidae). 20 records from A revision of the Patagonian predaceous midges of the subgenus Acanthohelea of Stilobezzia excluding the S. (A.) edwardsi group (Diptera: Ceratopogonidae). 2 records from New Vietnamese Species Of The Genus Flavoperla Chu (Plecoptera: Perlidae). 3 records from A new species of Arrhopalites Börner, 1906 (Collembola, Symphypleona, Arrhopalitidae) from Iran with an updated key to A. diversus group of species. 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 3 records from Two new cavernicolous Pselaphinae (Coleoptera: Staphylinidae) from southern China. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 3 records from A peculiar new species of the genus Grammacephalus Haupt (Hemiptera Auchenorrhyncha: Cicadellidae: Deltocephalinae) from Madagascar. 165 records from Nine new species of Enithares (Heteroptera: Notonectidae) from New Guinea, with distributional notes on other species and an updated world checklist. 6 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 17 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 3 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 15 records from Pelagic ctenophores from the São Sebastião Channel, southeastern Brazil. 30 records from Two new species of Odontostilbe historically hidden under O. microcephala (Characiformes: Cheirodontinae). 53 records from CHAS Botany Collection (Arctos). 10 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 4 records from Leuctra Pinhoti, A New Species Of Stonefly (Plecoptera: Leuctridae) From Alabama, U. S. A.. 7 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 3 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 87 records from Levinsenia species (Annelida: Polychaeta: Paraonidae) from the Sea of Marmara with descriptions of two new species. 11 records from A new species of Laurenceomyia Wagner & Stuckenberg, with a key to species and new records for Psychodidae (Diptera) from Uruguay. 2 records from Bryoerythrophyllum subcaespitosum (Pottiaceae), a new combination for a neglected species from South America. 19 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 54 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 222 records from The spider family Micropholcommatidae (Arachnida: Araneae: Araneoidea): a relimitation and revision at the generic level. 10 records from Oxynoemacheilus phasicus, a new nemacheilid loach from the eastern Black Sea basin with some remarks on other Caucasian Oxynoemacheilus (Teleostei: Nemacheilidae). 6 records from Revisions to the faunas of Andrena of the Iberian Peninsula and Morocco with the descriptions of four new species (Hymenoptera: Andrenidae). 326 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 65 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 1 records from Review of the genus Suwallia (Plecoptera: Chloroperlidae) from China with description of Suwallia jihuae sp. nov. from Sichuan Province. 3 records from Happywhale - Polar Bear in North Pacific Ocean. 15 records from Happywhale - Sei Whale in South Pacific Ocean. 13 records from New and noteworthy species of Begonia (Begoniaceae) from Vietnam and Laos. 6 records from The water striders (Hemiptera: Heteroptera: Gerridae) of Costa Rica: new species, checklist, and new records. 37 records from Two new species of Tipula (Vestiplex) Bezzi (Diptera, Tipulidae) from Northwest China. 7653 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 1 records from Species of Macrostomum (Macrostomorpha: Macrostomidae) from the coastal region of Lima, Peru, with comments on M. rostratum Papi, 1951. 3 records from Three squat lobsters (Crustacea: Decapoda: Anomura) from tropical West Pacific seamounts, with description of a new species of Uroptychus Henderson, 1888. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 1 records from Pseudotoothed Birds (Aves, Odontopterygiformes) from the Early Tertiary of Morocco. 2 records from Distribution extension of Calotes irawadi Zug, Brown, Schulte & Vindum, 2006, previously confused with C. versicolor (Daudin, 1802): first record from China. 9 records from Swedish Malaise Trap Project (SMTP) - Bethylidae. 5 records from The genus Enicospilus Stephens, 1835 (Hymenoptera, Ichneumonidae, Ophioninae) in Saudi Arabia, with twelve new species records and the description of five new species. 54 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 26 records from Composition of the genus Hanleya (Mollusca: Polyplacophora: Lepidopleurida), with the description of two new species. 4 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes Heptapteridae) from the Sierra Nevada de Santa Marta, Colombia. 7 records from Two new species of the genus Apsidophora Diakonoff, 1973 (Lepidoptera Tortricidae: Olethreutinae) from Thailand. 6 records from A taxonomic revision of the Palaearctic members of the Formica rufa group (Hymenoptera: Formicidae) - the famous mound-building red wood ants. 5 records from Happywhale - Southern Elephant Seal in Southern Ocean. 3 records from Distributional and taxonomic notes on the crab spider genus Talaus Simon, 1886 with description of a new species (Araneae: Thomisidae). 190 records from Herpetofauna laguna El Tinije. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 3 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 16 records from Revalidation of Acanthinozodium Denis, 1966 with description of three new species and discovery of a remarkable male palpal character (Araneae, Zodariidae). 3 records from A new species of the genus Dugesia (Tricladida: Dugesiidae) from China. 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 1 records from On Starengovia Snegovaya, a genus of Asian nemastomatines (Arachnida: Opiliones: Nemastomatidae). 8 records from Polycentropus dinkinsorum (Trichoptera: Polycentropodidae), a newly described caddisfly species from the southern Appalachian Mountains, USA. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 1 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 1 records from A new genus and species of Ingolfiellidae (Crustacea, Ingolfiellida) from the hyporheic zone in the Sierra de la Ventana, and its biogeographic relevance. 25 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 13518 records from MVZ Egg and Nest Collection (Arctos). 29 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 3 records from Differentiation among cave populations of the Eukoenenia spelaea species-complex (Arachnida: Palpigradi) in the southwestern Alps. 3 records from A new species of the genus Morimotanthribus Senoh & Trýzna (Coleoptera Anthribidae) from South China. 10 records from A new genus and species of cricket from eastern Cuba: the first Antillean true Eneopterinae (Orthoptera: Gryllidae: Eneopterinae). 1 records from New collections of freshwater crabs from northern Madagascar, with the description of a new species of Foza Reed & Cumberlidge, 2006 (Brachyura, Potamonautidae), and comments on their conservation status. 4 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 24104 records from VIS - Non-native fish in Flanders, Belgium. 4 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 5 records from A new cryptic species of Scorpiops Peters, 1861 (Scorpiones: Scorpiopidae) from the northern Western Ghats, India. 6 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 22 records from Five new and five known species of the genus Tylencholaimus de Man, 1876 (Nematoda: Dorylaimida: Tylencholaimoidea) from Western Ghats of India. 187 records from An annotated type catalogue of the centipedes (Myriapoda: Chilopoda) held in the Zoological Museum Hamburg. 2 records from Naturalis Biodiversity Center (NL) - Orthopteroidea. 89 records from Dragonflies (Odonata) From The Sierras Of Tapirapeco And Unturan, In The Extreme South Of Venezuela. 7 records from Taxonomy and evolution of asymmetric male genitalia in the subgenus Ashima Chen (Diptera: Drosophilidae: Phortica Schiner), with descriptions of seven new species. 1 records from A new and likely extinct species of Antilissus Sharp, 1879 (Coleoptera: Zopheridae Colydiinae) from Makauwahi Cave, Kauai, Hawaiian Islands. 618980 records from Hawk Migration Association of North America - HawkCount. 7 records from Deep into darkness: the first stygobitic species of freshwater shrimp of the genus Caridina (Crustacea: Decapoda: Atyidae) from Northern Vietnam. 4082 records from Meetnetten.be - Population counts for dragonflies in Flanders, Belgium. 3 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 63756 records from E. C. Smith Herbarium (ACAD). 2 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 29 records from Contribution to the Ichneumoninae (Hymenoptera, Ichneumonidae) of Nepal. 2 records from Un nouveau genre et une nouvelle espèce de Cigale aphone du Malawi (Rhynchota, Cicadidae, Cicadettinae). 1 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 20 records from New data on the taxonomy, distribution and host plants of Australian Epermeniidae (Lepidoptera: Epermenioidea). 3 records from A taxonomic revision of Globba subsect. Nudae (Zingiberaceae). 30 records from Uroptychus nitidus (A. Milne-Edwards, 1880) and related species (Crustacea: Decapoda: Anomura: Chirostylidae) from the western Atlantic. 2 records from A new species of Glyphocrangon (Crustacea, Decapoda, Caridea, Glyphocrangonidae) from the Austral Islands, French Polynesia. 10 records from Two new endangered species of Polygala series Trichospermae (Polygalaceae), endemic to the Cerrado domain, Tocantins State, Brazil. 139 records from Annotated checklist of bats (Mammalia: Chiroptera) of Mount Cameroon, southwestern Cameroon. 2 records from Multivariate discrimination and description of a new species of Tapinoma from the Western United States.. 12 records from Astyanax ajuricaba: a new species from the Amazon basin in Brazil (Characiformes: Characidae). 12630 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 7 records from A new apterous rove beetle genus (Coleoptera: Staphylinidae) from the Northern Andes with an assessment of its phylogenetic position. 4 records from Description of a new species of deep-water snake eel, Ophichthus mccoskeri (Ophichthidae: Ophichthinae) from Andaman Sea, India. 2 records from New records of brittle stars (Echinodermata: Ophiuroidea) from the Lakshadweep atolls, northern Indian Ocean, with notes on Indophioderma ganapatii Sastry Marimuthu & Rajan, 2019. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 11 records from Tokunagaia Saether from China (Diptera: Chironomidae: Orthocladiinae). 1 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 20897 records from Michigan State University Herbarium Lichens. 39 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 4 records from Review of Eotrogaspidia Lelej (Hymenoptera: Mutillidae: Trogaspidiini). 1 records from Limbodessus skalei sp. nov., a new diving beetle species from the west Papuan Archipelago (Coleoptera: Dytiscidae, Bidessini). 4 records from Thorectinae (Porifera: Demospongiae: Dictyoceratida) from Northeastern Brazil: two new species and transfer of Scalarispongia cincta (Boury-Esnault, 1973) to the genus Thorecta Lendenfeld, 1888. 60 records from Wichita State University Collection. 376028 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 1 records from Pitcairnia albifolia (Bromeliaceae), a new species from the Talamanca Mountains in Veraguas Province, Panama. 2 records from A new species and new records of Malagasy Megalopinus Eichelbaum (Coleoptera Staphylinidae, Megalopsidiinae), with notes on the sperm pump in rove beetles. 10 records from Four new species of the spider genus Cicurina Menge, 1871 from China (Araneae: Dictynidae). 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 2 records from A new species of Gamasellodes Athias-Henriot (Mesostigmata: Ascidae) from Brazil and a key to the world species of the genus. 9 records from Taxonomic review of the genus Assamacris (Orthoptera: Acrididae: Catantopinae) with a new species and a newly discovered female. 2 records from Eudraces barclayi sp. nov., with some notes on the genus Eudraces Marshall (Coleoptera: Curculionidae: Entiminae: Myorhinini). 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 159 records from Inventario de invertebrados marinos del SFF Isla Malpelo, Proyecto Colombia BIO. 1 records from Calidolipeurus, new genus for Lipeurus megalops Piaget, 1880 (Phthiraptera: Ischnocera: Oxylipeurus-complex), with a redescription of the type species and a preliminary key to the Oxylipeurus-complex. 4 records from Three new species and one new record of Torrenticolidae (Acari, Hydrachnidia) from Wuyishan with an updated key for Chinese fauna. 3 records from A new Central American genus of pleasing fungus beetles (Coleoptera: Erotylidae) from the Ischyrus-Megischyrus complex. 2 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 12 records from New Psocoptera (Hexapoda, Insecta) records from Belarus. 31 records from Three new widely distributed and polymorphic species of Amynthas earthworms (Oligochaeta, Clitellata, Megascolecidae) from South China. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 3 records from Happywhale - Northern Right Whale Dolphin in North Pacific Ocean. 2 records from Morphology and infraciliature of two new earthworm ciliates, Hoplitophrya polymorphus sp. nov. and Anoplophrya simplex sp. nov. (Ciliophora: Oligohymenophorea: Astomatia). 5 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 7 records from Genus Stathmopoda Herrich-Schäffer, 1853 (Lepidoptera: Stathmopodidae) from China: Descriptions of thirteen new species. 3 records from A new species of Auriculostoma (Trematoda: Allocreadiidae) from the intestine of Brycon guatemalensis (Characiformes: Bryconidae) from the Usumacinta River Basin, Mexico, based on morphology and 28 S rDNA sequences, with a key to species of the genus. 18 records from New and rare micro-pagurid hermit crabs (Crustacea: Anomura: Paguridae) from the Caribbean Sea and Gulf of Mexico. 9 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 11387 records from 16S data from: Diversity of Pico- to Mesoplankton along the 2000 km Salinity Gradient of the Baltic Sea (Hu et al. 2016). 5 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 22 records from Ahuyentamiento, rescate y reubicación de fauna en el área de influencia directa del proyecto Hidroeléctrico Mulatos II. 7 records from New species of ant-mimicking jumping spiders of the genus Myrmarachne MacLeay, 1839 (Araneae: Salticidae) from north Queensland, Australia. 2 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 2 records from Description of a new species of deep-sea spider crab from the genus Crocydocinus Lee, Richer de Forges & Ng, 2019, from the south-eastern Arabian Sea (Crustacea Decapoda: Majoidea: Epialtidae). 6 records from Anthopleura mariscali, a new species of sea anemone (Cnidaria: Anthozoa: Actiniaria) from the Galápagos Islands. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 10 records from A new species of Corydoras Lacépède, 1803 (Siluriformes: Callichthyidae) from the upper rio Paraná basin, Brazil. 4 records from A new species of Ephoron Williamson, 1802 (Ephemeroptera: Polymitarcyidae) from Thailand. 19 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 3 records from A remarkable new species of the genus Lepisiota Santschi (Hymenoptera: Formicidae) from Oman and the United Arab Emirates with a key to the Arabian species. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 24 records from Two new trans-Andean species of Imparfinis Eigenmann & Norris, 1900 (Siluriformes: Heptapteridae) from Colombia. 15 records from Three new species of Entomobrya from Poland (Collembola, Entomobryidae). 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 5 records from Two new Colombian harvestmen of the genus Quindina Roewer, 1914 (Opiliones Nomoclastidae). 26 records from Epimeria of the Southern Ocean with notes on their relatives (Crustacea, Amphipoda, Eusiroidea). 2 records from A new species of Hieracium sect. Pannosa (Asteraceae) from Bulgaria. 2 records from First description of the last instar larva and pupa of the aquatic crane fly Limnorimarga limonioides (Alexander, 1945) (Diptera: Limoniidae). 3 records from Nouveautés dans le genre Lomariopsis Fée (Pteridophyta, Lomariopsidaceae) à Madagascar: trois espèces nouvelles et une espèce africaine nouvellement signalée. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 3 records from New Morphological Observations And Phylogenetic Placement Of Capnia Shasta (Plecoptera: Capniidae). 116 records from Taxonomic revision of the Colombian Tityus (Archaeotityus) (Scorpiones, Buthidae) species: a morphological and morphometric approach, with a description of a new species. 2 records from Leptagrion itabaiana sp. nov. (Odonata: Coenagrionidae) from Serra de Itabaiana National Park, Sergipe state, Northeastern Brazil. 2 records from Yunnan-Guizhou Plateau: a mycological hotspot. 6 records from A New Species Of Perlesta (Plecoptera: Perlidae) From New York. 1 records from Review of the Oriental genus Neoperlops Banks, 1939 (Plecoptera: Perlidae). 1 records from Taxonomy and Natural History of Strumigenys thaxteri Wheeler and Strumigenys reticeps (Kempf) (Hymenoptera: Formicidae). 32 records from Siphonoecetinae (Crustacea: Amphipoda: Ischyroceridae) 7: Australian Concholestids, Ambicholestes n. gen., with a Description of Six New Species, and a New, Restricted Diagnosis for Caribboecetes Just, 1983. 24 records from Untangling the trees: Revision of the Calumma nasutum complex (Squamata: Chamaeleonidae). 3 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 11 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 1 records from On the Phylogenetic Placement of the Spider Genus Atimiosa Simon, 1895, and the Circumscription of Dolichognatha O. P. - Cambridge, 1869 (Tetragnathidae, Araneae). 2 records from Description of a new diminutive Hyloxalus (Anura: Dendrobatidae: Hyloxalinae) from the Magdalena Valley of Colombia. 1 records from A taxonomic note of Pterocephalus (Caprifoliaceae) from N Iran. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 2 records from Austrolebias varzeae, a new annual fish from the upper rio Uruguay basin, southern Brazil (Cyprinodontiformes: Rivulidae). 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 1 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 36 records from Occurrence of some antityphod plants from Cameroon. 2 records from A new canopy-dwelling species of Dendrelaphis (Serpentes: Colubridae) from Sinharaja, World Heritage Site, Sri Lanka. 56 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 76798 records from NMNH Paleobiology Specimen Records. 1 records from A new species and key to all known species of the genus Filchnerella Karny, 1908 from China (Orthoptera: Acridoidea, Pamphagidae). 15 records from New sponge species from Seno Magdalena, Puyuhuapi Fjord and Jacaf Canal (Chile). 1 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 24 records from Happywhale - Crabeater Seal in Southern Ocean. 4727 records from Zooplankton Species Distribution and Abundance Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise, August 2017. 1 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 51 records from A review of the genus Hexachaetoniella Paschoal in Australia (Acarina: Cryptostigmata: Pedrocortesellidae). 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 1989 records from NEON Biorepository Terrestrial Plant Collection (Belowground Biomass [Standard Sampling]). 4 records from Taxonomic review of the ant genus Dilobocondyla from China (Hymenoptera: Formicidae), with a revised key to the known species. 5 records from New species of Narberdia Burke from México and Central America (Coleoptera: Curculionidae). 15 records from Revision of the New World Panthea Hübner (Lepidoptera, Noctuidae) with descriptions of 5 new species and 2 new subspecies. 145445 records from Naturalis Biodiversity Center (NL) - Aves. 2 records from A new species of the genus Pseudocrangonyx (Crustacea: Amphipoda Pseudocrangonyctidae) from Simbok Cave, Korea. 1 records from A review of Labidostomis species similar to L. longimana from southeastern Europe with descriptions of two new species from Greece and Turkey (Coleoptera: Chrysomelidae: Cryptocephalinae: Clytrini). 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 1 records from Redescriptions, new synonymy, new combination and new records of Bacis Dejean, 1836 and Oligocorynus Dejean, 1876 (Coleoptera: Erotylidae: Erotylinae) for Colombia. 2844793 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 54 records from Capobula gen. nov., a new Afrotropical dark sac spider genus related to Orthobula Simon, 1897 (Araneae: Trachelidae). 518 records from Data from ILAM surveys conducted by ARCOS in Mukura landscape for year 2017. 228 records from Bishop's University Insect Collection (BUIC). 2 records from A new species of Dinotoperla Tillyard, 1921 from the Shoalhaven Catchment, New South Wales, Australia (Plecoptera: Gripopterygidae). 3 records from New species of Soa Enderlein, 1904 (Psocodea: ‘ Psocoptera’: Lepidopsocidae) from the Western Ghats of India. 25 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 9 records from New Oriental genera in the family Issidae (Hemiptera: Fulgoromorpha). 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 18 records from Happywhale - Blue Whale in Southern Ocean. 6606 records from Happywhale - Humpback Whale in North Atlantic Ocean. 105427 records from ABV - Common breeding birds in Flanders, Belgium (post 2016). 31 records from New species and additional data on the chewing louse genus Myrsidea (Phthiraptera: Menoponidae) from wild Neotropical Passeriformes (Aves). 3 records from Synonymy of the ant-loving cricket Myrmecophilus termitophilus Ma an, 1959 (Orthoptera: Myrmecophilidae). 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 25 records from Boreonemoral regnskog i Sveio. 5 records from Two new species of the genus Leeonychiurus Sun & Arbea, 2014 (Collembola: Onychiuridae) from Korea. 4 records from Descriptions of two new shell-dwelling species of Metriaclima (Cichlidae) from Lake Malaŵi, Africa. 10 records from Corynoneura Winnertz (Diptera, Chironomidae, Orthocladiinae) from Zhejiang Province, China. 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 5 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 363 records from The South American spider genera Mesabolivar and Carapoia (Araneae, Pholcidae): new species and a framework for redrawing generic limits. 14 records from Happywhale - Sperm Whale in South Atlantic Ocean. 3 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 24 records from Onysius Broun: The First New Zealand Genus Of Promecheilidae (Coleoptera: Tenebrionoidea). 3276325 records from Insecta of Costa Rica (INBio). 2 records from A new species of the genus Rapturella (Gastropoda: Acteonidae) from southeast Brazil. 5 records from Four new species of the leafhopper genus Riseveinus Li (Hemiptera: Cicadellidae: Evacanthinae) from China and Thailand. 8 records from A review of the Barbatula loaches (Teleostei: Nemacheilidae) from north-eastern China, with the description of four new species. 18 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 1 records from A new Schistura from an upper Mekong affluent in Yunnan (Teleostei: Nemacheilidae). 66 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 2 records from A pilot phylogeny study of Nemobiinae inferred from 18 S, 28 S and genes, with descriptions of two new genera and a new species from Hainan, China (Orthoptera: Grylloidea: Trigonidiidae). 2 records from Chalinochromis cyanophleps, a new species of cichlid fish (Teleostei: Cichlidae) from Lake Tanganyika. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 237709 records from Abundance of Rocky Reef Fishes, Invertebrates and Algae, Reef Check California (RCCA), 2006 - 2017. 5 records from Studies in Liocranidae (Araneae): redescriptions and transfers in Apostenus Westring and Brachyanillus Simon, as well as description of a new genus. 1 records from On several species of Oswaldella Stechow, 1919 (Cnidaria, Hydrozoa), including the description of a new species. 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 39438 records from National Biodiversity Data Bank. Observation records, 1900-2014. 334 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 28 records from Brentidae Acratini du massif du Mitaraka, en Guyane: une synthèse des données (Insecta, Coleoptera, Curculionoidea). 2 records from A new centipede Schendylops Cook from eastern Brazil: the first troglobitic geophilomorph for South America (Geophilomorpha, Schendylidae). 133 records from Schellenberg A. 1936. The fishery grounds near Alexandria. Amphipoda Benthonica. Notes and memoirs No 18.. 3 records from Hiding in plain sight on Gunung Muria: A new species and first record of rock gecko (Cnemaspis Strauch, 1887; Squamata, Gekkonidae) from Java, Indonesia. 235 records from Revision of the spider genus Stygopholcus (Araneae, Pholcidae), endemic to the Balkan Peninsula. 1 records from Two new species of Corynellus Bates, 1885 (Coleoptera: Cerambycidae: Cerambycinae). 1 records from A new species of ‘ Bird’s Nest’Anthurium sect. Pachyneurium (Araceae) from Brazil. 2 records from A new species of the genus Thoracochirus Bernhauer (Coleoptera: Staphylinidae: Osoriinae) from Yunnan, China. 4 records from First records of Dentridactylinae (Orthoptera: Tridactylidae) from Colombia, with description of two new species of Dentridactylus Günther. 42631 records from Physical and biological data collected along the Texas, Louisiana, Mississippi, Alabama, and Florida Gulf coasts in the Gulf of Mexico as part of the Harmful Algal BloomS Observing System. 5 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 54 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 5 records from A new species of Hedya Hübner from Iran with proposed rearrangement of some species currently assigned to Metendothenia Diakonoff (Lepidoptera: Tortricidae). 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 1 records from A new species of Hemidactylus (Squamata: Gekkota: Gekkonidae) from Qara Dagh Mountains, Kurdistan Region, with a key to the genus in Iraq. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 6 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 19 records from A new species of whiptail armored catfish, genus Pseudohemiodon (Siluriformes: Loricariidae) from the Orinoco River basin, Llanos region of Colombia and Venezuela. 424 records from Collection de C.C.H. Jongkind aux Monts Nimba. 3 records from Persianorchestia, a new talitrid genus (Crustacea: Amphipoda: Talitridae) from Gulf of Oman, Iran. 2 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 4 records from Yunnanosticta gen. nov., from Yunnan, a new genus from the Sinostictinae, with the description of two new species (Odonata: Zygoptera: Platystictidae). 4 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 8 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 6 records from A new species of Parathyone (Holothuroidea: Dendrochirotida: Cucumariidae) from northeastern Brazil, with a key to species. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 41698 records from Herbier National du Gabon. 3 records from Alpheus luiszapatai, a new species of rare and colorful deep water alpheid shrimp (Crustacea: Decapoda: Alpheidae) from Arusí, Chocó Department, Pacific Coast of Colombia. 4 records from Afrotropical flower flies (Diptera: Syrphidae). A new genus and species from Kenya, with a review of the melanostomine group of genera. 1 records from Review of six genera of Braconinae Nees (Hymenoptera, Braconidae) in China, with the description of eleven new species. 17 records from New species and additional records of Cephalocousya and Drepasiagonusa from China and Russia (Coleoptera: Staphylinidae: Aleocharinae: Oxypodini). 1 records from Morphology and infraciliature of a new marine ciliate, Cinetochilum ovale n. sp. (Ciliophora: Oligohymenophorea). 1 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 5 records from New data and species of Thecomyia Perty, 1833 (Diptera: Sciomyzidae) from Mitaraka (French Guiana), with notes on the genus. 33 records from New species and records of Perlidae (Plecoptera) from Espírito Santo State, Brazil. 57 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 1 records from A revision of the genus Lepidobrya Womersley (Collembola: Entomobryidae) based on morphology and sequence data of the genotype. 35 records from The Italian species of the Chthonius ischnocheles group (Arachnida, Pseudoscorpiones, Chthoniidae), with reference to neighbouring countries. 1 records from A review of the North American species of the fungus-gardening ant genus Trachymyrmex (Hymenoptera: Formicidae).. 12 records from A new genus and two new species of miniature clingfishes from temperate southern Australia (Teleostei, Gobiesocidae). 2 records from Distributions and Variations of Two Estuarine Species of Composetia (Annelida: Nereididae) in the Ryukyu Islands, Southern Japan, with a New Record of Composetia tokashikiensis from Thailand. 1 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 3 records from Aphelocheirus (s. str.) gusenleitneri nov. sp. - Erstnachweis der Aphelocheiridae (Heteroptera) aus Myanmar. 10 records from Congruence between morphology and molecular data supports the distinction between the snapping shrimps Alpheus macrocheles and A. amblyonyx (Caridea, Alpheidae). 5 records from Two new nematode species of the genus Tobrilus Andrássy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 7 records from On the Turkish species of Sunius. VII. Five new micropterous species from western Anatolia and additional records (Coleoptera: Staphylinidae, Paederinae). 3 records from Gibbosaverruca weijiai, a new verrucid (Crustacea, Thoracica) species from the Weijia Guyot deep-sea seamount in the West Pacific. 10 records from Two new species of armoured spiders from Vietnam and Cambodia (Araneae: Tetrablemmidae: Pacullinae). 3 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 7 records from Revision of the genus Hormoserphus Townes, 1981 (Hymenoptera: Proctotrupidae), with description of Trachyserphus gen. n. and a new species. 10 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 7 records from Update of the genus Leptochiton (Mollusca: Polyplacophora) in Chilean deep waters: three new reports and description of two new species. 8 records from Bolbelasmus (Bolbelasmus) zagrosensis (Coleoptera: Scarabaeoidea: Bolboceratidae), a new species from Iran, along with an updated key to the western Palaearctic species of the subgenus. 138 records from Hermit crabs of the family Parapaguridae (Crustacea: Decapoda: Anomura) from Australia: species of Strobopagurus Lemaitre, 1989, Sympagurus Smith, 1883 and two new genera.. 4 records from Complementary Descriptions Of Kempnyia Gracilenta (Enderlein 1909) And Kempnyia Reticulata (Klapálek 1916) (Plecoptera: Perlidae). 3 records from Three new species of genus Pylaemenes Stål (Phasmatodea: Heteropterygidae: Dataminae) from Vietnam. 1 records from First Record Of Pseudepipona Kazenasi Kurzenko, 1974 (Hymenoptera: Vespidae) From Mongolia. 8 records from Notes on rattans (Arecaceae) from Vietnam. 25 records from Re-description of Strandesia sanoamuangae Savatenalinton
Keywords: GBIF; biodiversity; species occurrences